Liquid crystal aligning agent, liquid crystal alignment film, liquid crystal element, and compound
By using a combination of diamines with benzophenone structure and other polymers in the liquid crystal alignment agent, an optimized liquid crystal alignment film is formed, which solves the problems caused by impurities invasion and long light exposure time in the liquid crystal element, and improves the resistance of the liquid crystal element Impurity and display performance.
Patent Information
- Application Number
- CN202410791395.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-06-19
- Publication Date
- 2024-12-31
AI Technical Summary
In the process of high-finement and multi-purpose liquid crystal components, there are problems such that ionic impurities introduced by the insulating films lead to a decrease in voltage retention rate and an increase in accumulation of charges, and the PSA-type liquid crystal components have photopolymerizable compounds during light irradiation. The polymerization reaction causes a change in the pretilt angle, and the long light exposure time may damage the liquid crystal unit.
A liquid crystal alignment agent is adopted, including diamine with benzophenone structure as side chain units of the polymer, and combined with free polyamic acid, polyimide, polyorganosiloxane and addition polymer, through crossing The coupling agent forms a liquid crystal alignment film, optimizes the impurity resistance, inclination impartment properties and sealing material bonding of the liquid crystal alignment film, and shortens the light irradiation time.
The impurity resistance, inclination impartment properties and sealing material bonding of the liquid crystal orientation film are improved, the light irradiation time of the PSA-type liquid crystal element is shortened, the damage to the liquid crystal unit by light irradiation is reduced, and the display quality and stability are improved.
Smart Images

Figure CN119220270A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal alignment agent, a liquid crystal alignment film, a liquid crystal element and a compound. Background Art
[0002] As liquid crystal elements, a variety of driving modes with different electrode structures or physical properties of liquid crystal molecules have been developed, for example, there are various liquid crystal elements such as twisted nematic (TN) type or super twisted nematic (STN) type, vertical alignment (VA) type, multi-domain vertical alignment (MVA) type, in-plane switching type (IPS (In-Plane Switching) type), fringe field switching (FFS) type, optically compensated bend type (OCB (Optically Compensated Bend) type). These liquid crystal elements have a liquid crystal alignment film for aligning the liquid crystal molecules. The liquid crystal alignment film is usually formed on the substrate by applying a liquid crystal alignment agent obtained by dissolving or dispersing a polymer component in an organic solvent to the surface of the substrate, preferably by heating.
[0003] Previously known techniques for imparting a pretilt angle to liquid crystal molecules include: a rubbing method, in which the surface of a coating formed from a liquid crystal alignment agent is rubbed in a certain direction using a cloth or the like; and a photoalignment method, in which a photosensitive coating is irradiated with radiation. Furthermore, a method (Polymer Sustained Alignment (PSA)) has been proposed, in which a photopolymerizable compound is pre-added to the liquid crystal and then irradiated with radiation while applying a voltage to the liquid crystal cell to impart a pretilt angle to the liquid crystal molecules near the liquid crystal alignment film. PSA technology can improve the response speed of liquid crystal molecules and increase transmittance.
[0004] With the recent demand for higher precision and more versatile liquid crystal elements, liquid crystal elements are required to further improve their electrical properties and display quality. To achieve this, various liquid crystal alignment agents have been proposed (for example, see Patent Document 1). Patent Document 1 discloses that a free radical generating structure that generates free radicals upon light absorption is introduced into a polymer component constituting a liquid crystal alignment film, thereby improving the response speed of the liquid crystal in a PSA-type liquid crystal display element.
[0005] [Prior art literature]
[0006] [Patent Document]
[0007] [Patent Document 1] International Publication No. 2015 / 033921 Summary of the Invention
[0008] [Problems to be solved by the invention]
[0009] As liquid crystal elements become more refined, the requirements for quality become more stringent. For example, an insulating film is mostly provided on high-precision liquid crystal panels such as 4K or 8K. On the other hand, in a liquid crystal panel provided with an insulating film, ionic impurities from the insulating film are sometimes dissolved into the liquid crystal via the liquid crystal alignment film. In the case where ionic impurities are dissolved into the liquid crystal, there is concern that the quality of the liquid crystal element may be reduced due to a decrease in voltage holding ratio or an increase in accumulated charge. Therefore, the liquid crystal alignment film is required to inhibit impurities generated in the element from invading the liquid crystal, and is not prone to the characteristics of reducing the quality of the liquid crystal element due to impurities (hereinafter also referred to as "impurity resistance"). In addition, when considering the use for manufacturing PSA-type liquid crystal elements, it is ideal that the desired pre-tilt angle (hereinafter also referred to as "tilt imparting property") can be imparted by as little irradiation amount as possible when the liquid crystal unit is irradiated with light.
[0010] In high-precision liquid crystal elements, a liquid crystal alignment film that not only further improves impurity resistance or tilt imparting properties, but also has excellent mechanical properties or adhesion to substrates is sought. For example, from the perspective of design or the miniaturization of display devices, in addition to mobile applications represented by smart phones or tablet PCs, narrow frame is also being realized in large-scale TVs or PC monitors. As one of the methods for realizing narrow frame, it is known that after forming a liquid crystal alignment film on the entire substrate surface, a sealant is applied to the liquid crystal alignment film to adhere the substrates to each other. On the other hand, if a sealant is configured on the liquid crystal alignment film, it is easy to apply force to the liquid crystal alignment film portion configured with the sealant, so when the mechanical strength of the liquid crystal alignment film or the adhesion to the substrate is not sufficient, there is the following concern: resulting in a decrease in adhesion between substrates (hereinafter also referred to as "sealant adhesion"), and the peeling of substrates is easily produced due to the action of external forces.
[0011] In a PSA-type liquid crystal element, if a photopolymerizable compound remains in the liquid crystal layer, there is a concern that the pretilt angle of the liquid crystal may change over time due to the polymerization reaction of the remaining photopolymerizable compound. Therefore, in the manufacturing process of a PSA-type liquid crystal element, sometimes after performing light irradiation to impart a pretilt angle to the liquid crystal (hereinafter referred to as "first irradiation"), the liquid crystal cell is irradiated with light of equal or weaker intensity than the first irradiation for a long time (for example, about 100 minutes) without applying a voltage to the liquid crystal cell in order to consume the photopolymerizable compound in the liquid crystal. It is believed that by extending the light irradiation time based on the second irradiation, the consumption of the photopolymerizable compound in the liquid crystal layer can be promoted. On the other hand, there is a concern that the damage caused to the liquid crystal cell by the prolonged second irradiation will increase. In order to minimize the damage caused to the liquid crystal cell by the second irradiation, it is ideal to shorten the light irradiation time based on the second irradiation as much as possible and consume the photopolymerizable compound in the liquid crystal through the second irradiation, thereby suppressing the change of the pretilt angle over time.
[0012] The present invention is made in view of the above-mentioned problems, and its main purpose is to provide a liquid crystal alignment agent, which can obtain a liquid crystal alignment film with excellent impurity resistance, tilt imparting properties and sealing material adhesion, and can shorten the light irradiation time of the liquid crystal unit when manufacturing PSA type liquid crystal elements.
[0013] [Technical means to solve the problem]
[0014] According to this invention, the following liquid crystal aligning agent, liquid crystal aligning film, liquid crystal element, and compound can be provided.
[0015] [1] A liquid crystal alignment agent comprising: a first polymer comprising a polymer having "*-X 1 -W 1 " represented by the group (wherein, X 1 is a divalent linking group; W 1 is a monovalent group having a benzophenone structure; "*" represents a bonding bond) and has "*-X 1 -W 1 " represented by the group; and the second polymer is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane and addition polymer and does not substantially contain a structural unit having a benzophenone structure, and at least one selected from the group consisting of the first polymer and the second polymer contains a group having a secondary amino group, a tertiary amino group, * 1 -NR 1 -* 2 and at least one nitrogen-containing structure in the group consisting of nitrogen-containing heterocyclic structures (wherein R 1Is a monovalent detached group; "* 1 "and"* 2 " represents a structural unit of a diamine (bonded to a carbon atom excluding the carbon in the (thio)carbonyl group).
[0016] [2] A liquid crystal alignment agent comprising: a polymer comprising a polymer having "*-X 1 -W 1 " represented by the group (wherein, X 1 is a divalent linking group; W 1 is a monovalent group having a benzophenone structure; "*" represents a bonding bond) and has "*-X 1 -W 1 " represented by; and a cross-linking agent.
[0017] [3] A liquid crystal alignment film formed using the liquid crystal alignment agent according to [1] or [2].
[0018] [4] A liquid crystal element comprising the liquid crystal alignment film according to [3].
[0019] [5] A compound represented by the following formula (CA-1-1).
[0020] [Chemistry 1]
[0021]
[0022] (In the formula (CA-1-1), R 8 is an alkanediyl group having 1 to 10 carbon atoms; Z 1 is an oxygen atom or -NR 9 -;R 9 is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group; R 5 and R 6 are independently monovalent substituents; r1 is an integer from 0 to 4; r2 is an integer from 0 to 5)
[0023] [Effects of the Invention]
[0024] The liquid crystal aligning agent of the present invention can provide a liquid crystal aligning film having excellent impurity resistance, tilt imparting properties, and sealant adhesion. Furthermore, the liquid crystal aligning agent of the present invention can shorten the light irradiation time for the liquid crystal cell when producing a PSA type liquid crystal element. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the 1H-NMR spectrum of compound (DA-3). DETAILED DESCRIPTION
[0026] The liquid crystal alignment agent disclosed herein contains a polymer including a structural unit derived from a specific diamine having a benzophenone structure and having a benzophenone structure in a side chain. Specific embodiments of the liquid crystal alignment agent disclosed herein include the following first and second liquid crystal alignment agents.
[0027] The first liquid crystal alignment agent comprises a first polymer and a second polymer, wherein the first polymer comprises a polymer having "*-X 1 -W 1 " is a structural unit of a diamine group represented by a group and has "*-X 1 -W 1 ", the second polymer is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane and addition polymer and substantially does not contain a structural unit having a benzophenone structure. At least one selected from the group consisting of the first polymer and the second polymer contains a group having a secondary amino group, a tertiary amino group, 1 -NR 1 -* 2 and a diamine structural unit of at least one nitrogen-containing structure (hereinafter also referred to as "nitrogen-containing structure FN") in the group consisting of a nitrogen-containing heterocyclic structure. 1 -W 1 "In the basis represented by 1 is a divalent linking group, W 1 It is a monovalent group with a benzophenone structure, and "*" represents a bonding bond (the same applies below). 1 -NR 1 -* 2 In the basis represented by 1 It is a monovalent detached group, “* 1 "and"* 2 " represents a bond to a carbon atom excluding the carbon in the (thio)carbonyl group.
[0028] The second liquid crystal alignment agent: contains a polymer and a cross-linking agent, wherein the polymer comprises a cross-linking agent having "*-X 1 -W 1 " is a structural unit of a diamine group represented by a group and has "*-X 1 -W 1 "The base represented by ".
[0029] Hereinafter, the first liquid crystal aligning agent which is the first embodiment of the liquid crystal aligning agent of the present disclosure and the second liquid crystal aligning agent which is the second embodiment will be described respectively.
[0030] Here, in this specification, the so-called "hydrocarbon group" means a chain hydrocarbon group, an alicyclic hydrocarbon group and an aromatic hydrocarbon group. The so-called "chain hydrocarbon group" refers to a straight-chain hydrocarbon group and a branched hydrocarbon group that does not contain a cyclic structure in the main chain but only contains a chain structure. Among them, the chain hydrocarbon group may be saturated or unsaturated. The so-called "alicyclic hydrocarbon group" refers to a hydrocarbon group that only contains an alicyclic hydrocarbon structure as a ring structure and does not contain an aromatic ring structure. Among them, the alicyclic hydrocarbon group does not need to contain only an alicyclic hydrocarbon structure, and also includes a group with a chain structure in a part thereof. The so-called "aromatic hydrocarbon group" refers to a hydrocarbon group that contains an aromatic ring structure as a ring structure. Among them, the aromatic hydrocarbon group does not need to contain only an aromatic ring structure, and may also contain a chain structure or an alicyclic hydrocarbon structure in a part thereof. The meaning of "aromatic ring" includes an aromatic hydrocarbon ring and an aromatic heterocycle. The so-called "organic group" refers to an atomic group formed by removing any hydrogen atom from a compound containing carbon (i.e., an organic compound).
[0031] The term "main chain" of a polymer refers to the "trunk" portion of the polymer containing the longest atomic chain. This "trunk" portion may contain a ring structure. For example, "having a specific structure in the main chain" means that the specific structure constitutes a portion of the main chain. The term "side chain" refers to a portion branching from the "trunk" of a polymer. "(Thio)carbonyl" encompasses both carbonyl and thiocarbonyl groups.
[0032] The first liquid crystal alignment agent
[0033] The first liquid crystal aligning agent contains the first polymer and the second polymer. In addition, unless otherwise specified, each component contained in the liquid crystal aligning agent may be used alone or in combination of two or more.
[0034] The first polymer is available as long as it contains a polymer derived from a polymer having "*-X 1 -W 1 " is a polymer of structural units of diamines represented by a group, and the type of its main skeleton is not particularly limited. The first polymer is preferably a condensation polymer obtained by using a monomer containing a diamine compound, for example, polyamic acid, polyamic acid ester, polyimide, polyamide, polyamideimide, etc. From the perspective of obtaining a liquid crystal element with excellent liquid crystal orientation and electrical properties and from the perspective of having "*-X 1 -W 1 From the viewpoint of ease of introduction of a diamine structural unit having a group represented by ", the first polymer is preferably at least one selected from the group consisting of polyamic acid and polyimide, and more preferably polyamic acid.
[0035] The second polymer is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane and addition polymer. By setting the second polymer as the polymer, the biased existence of the first polymer in the film is promoted, thus the tilt imparting property can be improved. When the first polymer is a polyimide, with respect to the effect of improving the tilt imparting property of the liquid crystal alignment film and the sealant adhesion, the second polymer is preferably at least one selected from the group consisting of polyamic acid, polyorganosiloxane and addition polymer, with respect to the aspect of the reduction effect of further improving residual direct current (Direct Current, DC), and then preferably polyamic acid. The second polymer does not substantially include the structural unit with benzophenone structure, is different from the first polymer in this respect.
[0036] Furthermore, the second polymer may contain a small amount of structural units having a benzophenone structure, within a range that does not impair the effects of the present invention. Specifically, in the second polymer, the content of structural units having a benzophenone structure is preferably less than 0.5 mol%, more preferably less than 0.1 mol%, and even more preferably 0 mol%, relative to the total amount of structural units derived from monomers constituting the second polymer.
[0037] As a preferable aspect of the combination of the 1st polymer and the 2nd polymer contained in a liquid crystal aligning agent, the following [Aspect 1A] - [Aspect 4A] are mentioned.
[0038] [Aspect 1A] The first polymer and the second polymer are in the form of polyamic acid.
[0039] [Aspect 2A] The first polymer is polyamic acid, and the second polymer is a polyamic acid and a polyorganosiloxane or an addition polymer.
[0040] [Aspect 3A] Aspect 3A wherein the first polymer is polyamic acid and the second polymer is at least one selected from the group consisting of polyimide, polyorganosiloxane, and addition polymer.
[0041] [Aspect 4A] Aspect in which the first polymer is polyimide and the second polymer is at least one selected from the group consisting of polyamic acid, polyorganosiloxane, and addition polymer.
[0042] From the perspective of promoting the partial presence of the first polymer in the film to further improve the tilt-imparting property, among the above, [Form 1A], [Form 2A] or [Form 3A] is preferred. From the perspective of obtaining a liquid crystal alignment film with excellent tilt-imparting property and sealing material adhesion, [Form 1A] is more preferred.
[0043] In the first liquid crystal alignment agent, the first polymer comprises 1 -W1 " In addition, one or both of the first polymer and the second polymer contain a structural unit derived from a diamine having a nitrogen-containing structure FN.
[0044] In the case where the first polymer includes a structural unit derived from a diamine having a nitrogen-containing structure FN, the first polymer may also include a structural unit derived from a diamine having a "*-X 1 -W 1 " and the structural unit of the diamine having a nitrogen-containing structure FN and not having "*-X 1 -W 1 ". In addition, the first polymer may also contain a diamine structural unit derived from a group having "*-X 1 -W 1 " and a structural unit of a diamine having a nitrogen-containing structure FN. From the perspective of ease of synthesis of the monomer, when the first polymer contains a structural unit derived from a diamine having a nitrogen-containing structure FN, the first polymer preferably also contains a structural unit derived from a diamine having "*-X 1 -W 1 " and the structural unit of the diamine having a nitrogen-containing structure FN and not having "*-X 1 -W 1 " is a structural unit of a diamine group represented by ".
[0045] Furthermore, in the case where the second polymer is a polyorganosiloxane or an addition polymer, the first polymer includes a structural unit derived from a diamine having a nitrogen-containing structure FN.
[0046] One or both of the first polymer and the second polymer may also have a 1 -W 1 " is a functional group different from the group represented by the nitrogen-containing structure FN. In terms of further improving the tilt-imparting property of the liquid crystal alignment film, one or both of the first polymer and the second polymer preferably contains a structural unit having a vertical alignment group.
[0047] The structural unit having a vertical alignment group may be contained in the first polymer, may be contained in the second polymer, or may be contained in both the first polymer and the second polymer. In addition, when the structural unit having a vertical alignment group is a structural unit derived from a diamine, the diamine providing the structural unit having a vertical alignment group may not have "*-X 1 -W 1 " and the diamine of any one of the nitrogen-containing structure FN may be a diamine having "*-X 1 -W 1 " and a diamine of at least one of the group represented by and the nitrogen-containing structure FN.
[0048] For example, when the first polymer includes a structural unit derived from a diamine having a vertical alignment group, the first polymer may also include a structural unit derived from a diamine having "*-X 1 -W 1 " and the structural unit derived from a diamine having a vertical alignment group and not having "*-X 1 -W 1 ". In addition, the first polymer may also contain a diamine structural unit derived from a group having "*-X 1 -W 1 " and a diamine structural unit of a vertical alignment group, the first polymer may also contain a diamine structural unit derived from a diamine having "*-X 1 -W 1 " is a structural unit of a diamine having a vertical alignment group, a nitrogen-containing structure FN and a vertical alignment group. From the perspective of ease of synthesis of the monomer and ease of adjustment of the content of each functional group in the polymer, when the first polymer contains a structural unit derived from a diamine having a vertical alignment group, the first polymer preferably also contains a structural unit derived from a diamine having "*-X 1 -W 1 " and the structural unit derived from a diamine having a vertical alignment group and not having "*-X 1 -W 1 " is a structural unit of a diamine group represented by ".
[0049] From the perspective of improving the tilt-imparting property of the liquid crystal alignment film, it is preferred that at least the first polymer contains a structural unit having a vertical alignment group. From the perspective of ease of synthesis, the structural unit having a vertical alignment group in the first polymer is more preferably a structural unit derived from a diamine having a vertical alignment group.
[0050] One or both of the first polymer and the second polymer may further include a structural unit derived from a diamine having a *-NR bonded to an aromatic ring. 2 -CO- or *-CO-NR 2 -partial structure (wherein, R 2 is a hydrogen atom or a monovalent organic group, "*" represents a bond to an aromatic ring) as a 1 -W 1 "The functional groups represented by the groups and nitrogen-containing structures FN are different. By bonding *-NR 2 -CO- or *-CO-NR 2 The partial structure of - is introduced into the polymer component, and the effect of suppressing the accumulation of charges in the liquid crystal element can be further enhanced.
[0051] *-NR is bonded to the aromatic ring 2-CO- or *-CO-NR 2 -partial structure can be introduced into the main chain of one or both of the first polymer and the second polymer, or into the side chain. 2 -CO- or *-CO-NR 2 - is introduced into the main chain, and the remaining part is introduced into the side chain. 2 -CO- or *-CO-NR 2 - The diamine of the structural unit of the partial structure may be not having "*-X 1 -W 1 ", a diamine of any one of the nitrogen-containing structure FN and the vertical alignment group, may also be a diamine having "*-X 1 -W 1 " A diamine of at least any one of a group represented by, a nitrogen-containing structure FN and a vertical alignment group.
[0052] For example, in the case where the first polymer comprises a polymer having a *-NR bonded to an aromatic ring 2 -CO- or *-CO-NR 2 -In the case of a diamine structural unit having a partial structure of "*-X 1 -W 1 " and the diamine structural unit derived from a diamine having a *-NR bonded to the aromatic ring. 2 -CO- or *-CO-NR 2 -partial structure and does not have "*-X 1 -W 1 ". In addition, the first polymer may also contain a diamine structural unit derived from a group having "*-X 1 -W 1 "The group represented by *-NR is bonded to the aromatic ring. 2 -CO- or *-CO-NR 2 - is a structural unit of a diamine having a partial structure.
[0053] In addition, when the second polymer is a polyorganosiloxane or an addition polymer, the first polymer preferably contains a polymer having a *-NR bonded to an aromatic ring. 2 -CO- or *-CO-NR 2 - is a structural unit of a diamine having a partial structure.
[0054] Next, the first liquid crystal aligning agent is contained in the polymer component, and the 1 -W 1", a structural unit derived from a diamine having a nitrogen-containing structure FN, a structural unit having a vertical alignment group, and a structural unit derived from a diamine having a *-NR bonded to an aromatic ring. 2 -CO- or *-CO-NR 2 -The details of the structural unit of the diamine of the partial structure are described separately. In addition, below, for convenience, the structural unit derived from the diamine having "*-X 1 -W 1 The structural unit of the diamine containing a group represented by " is referred to as "structural unit (UA)", the structural unit derived from the diamine having a nitrogen-containing structure FN is referred to as "structural unit (UB)", the structural unit having a vertical alignment group is referred to as "structural unit (UC)," and the structural unit derived from the diamine having a *-NR bonded to the aromatic ring is referred to as "structural unit (UA)". 2 -CO- or *-CO-NR 2 -partial structure of diamine is called "structural unit (UD)". Each structural unit may have multiple functional groups. For example, structural unit (UA) may also have "*-X 1 -W 1 " and nitrogen-containing structure FN. With "*-X 1 -W 1 The structural unit of the group represented by " and the nitrogen-containing structure FN can be a structural unit (UA) or a structural unit (UB). In addition, similarly, the group represented by "*-X 1 -W 1 The structural unit of the group represented by " and the vertical alignment group may be a structural unit (UA) or a structural unit (UC).
[0055] About structural unit (UA)
[0056] The first polymer has a structural unit (UA) derived from a 1 -W 1 " represented by the group (wherein, X 1 is a divalent linking group, W 1 is a monovalent group having a benzophenone structure; "*" represents a bonding bond) of a diamine structural unit. 1 Examples of the divalent linking group represented by include: -O-, -CO-O-* 1 、-O-CO-* 1 、-NR 3 -CO-* 1 、-CO-NR 3 -* 1 、-Y 1 -R 7 -Y 2 -* 1 、-R 8 -Z1 -* 1 wait.
[0057] Here, in X 1 In the divalent linking group represented by 3 R is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. 7 is a divalent chain hydrocarbon group having 1 to 20 carbon atoms, a divalent alicyclic hydrocarbon group having 3 to 20 carbon atoms, or a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms. 7 It is preferably a divalent chain hydrocarbon group having 1 to 20 carbon atoms, and more preferably an alkanediyl group having 1 to 10 carbon atoms. 1 and Y 2 Independently -O-, -CO-O-* 2 、-O-CO-* 2 、-NR 4 -CO-* 2 or -CO-NR 4 -* 2 . R 4 R is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. 8 is an alkanediyl group having 1 to 10 carbon atoms. 8 It is preferably an alkanediyl group having 1 to 3 carbon atoms. 1 is an oxygen atom or -NR 9 -. R 9 It is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group. 1 " indicates that 1 The bonding bond. 2 " represents a bond to an alkanediyl group. In addition, "*-X 1 -W 1 The group represented by " can be arranged on the side chain of the first polymer.
[0058] R 9 The monovalent thermally detachable group represented is an organic group that is detached by heat. As the thermally detachable group, for example, carbamate-based detachable groups, amide-based detachable groups, imide-based detachable groups, sulfonamide-based detachable groups, etc. can be cited. Among these, in terms of high thermal detachability, carbamate-based detachable groups are preferred. As specific examples of carbamate-based detachable groups, tert-butoxycarbonyl, benzyloxycarbonyl, 1,1-dimethyl-2-halogenated ethyloxycarbonyl, allyloxycarbonyl, 2-(trimethylsilyl)ethoxycarbonyl, 9-fluorenylmethyloxycarbonyl (F-moc group) and the like can be cited. In terms of excellent thermal detachability and the ability to reduce the residual amount of the deprotected portion in the film, among these, tert-butoxycarbonyl (Boc group) is particularly preferred.
[0059] The diamine providing the structural unit (UA) (hereinafter also referred to as "first diamine") is preferably an aromatic diamine. The two primary amino groups in the first diamine are preferably bonded to the same aromatic ring, more preferably bonded to the same benzene ring (i.e., having a diaminophenyl group). When the first diamine has a diaminophenyl group, the bonding position of the amino group bonded to the benzene ring is not particularly limited, and examples thereof include relative to other groups ("*-X 1 -W 1 ") and is 2,4-position, 2,5-position or 3,5-position. Among these, 2,4-position or 3,5-position is preferred.
[0060] The benzophenone structure consists of two benzene rings linked via a carbonyl group. In the benzophenone structure of the first diamine, a substituent may be bonded to the benzene ring. Examples of such substituents include halogen atoms, alkyl groups, alkoxy groups, hydroxyl groups, vertically aligning groups, and groups having a nitrogen-containing structure (FN).
[0061] As a preferable specific example of the 1st diamine, the compound represented by following formula (CA-1) is mentioned.
[0062] [Chemistry 2]
[0063]
[0064] (In formula (CA-1), X 1 is a divalent linking group; X 2 Is a single key or has "*-X 1 -W 1 " represents a divalent group of the partial structure; R 5 and R 6 are independently monovalent substituents; r1 is an integer from 0 to 4; r2 is an integer from 0 to 5)
[0065] In the formula (CA-1), R 5 Examples of the monovalent substituent represented by include halogen atoms, alkyl groups, alkoxy groups, and hydroxyl groups. 6 Examples of the monovalent substituent include a halogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a vertical alignment group, and a group having a nitrogen-containing structure FN.
[0066] From the perspective of ease of monomer synthesis, X 2 It is preferably a single bond.
[0067] X 1 Specific examples of the bonding positions of the divalent linking group and the two primary amino groups are as described above.
[0068] More specific examples of the first diamine include compounds represented by the following formulae (C1-1) to (C1-24). In the formulae, "Boc" represents a tert-butoxycarbonyl group (the same shall apply hereinafter).
[0069] [Chemistry 3]
[0070]
[0071] [Chemistry 4]
[0072]
[0073] The content ratio of the structural unit (UA) in the first polymer is preferably 1 mol% or more, more preferably 2 mol% or more, and further preferably 5 mol% or more, relative to the total amount of the structural units derived from the monomers constituting the first polymer. In addition, the content ratio of the structural unit (UA) is preferably 50 mol% or less, more preferably 30 mol% or less, relative to the total amount of the structural units derived from the monomers constituting the first polymer. If the content ratio of the structural unit (UA) in the first polymer is within the above range, better tilt imparting properties can be ensured, and a liquid crystal element in which the time-dependent change of the pretilt angle is suppressed can be obtained while shortening the irradiation time of the second irradiation when manufacturing a PSA-type liquid crystal element.
[0074] In addition, the compound represented by the formula (C1-14) or formula (C1-15) and the compound represented by each of the formulas (C1-20) to (C1-22) are compounds having "*-X 1 -W 1 "The diamine of the group represented by " and the nitrogen-containing structure FN. 1 -W 1 The ratio of the group represented by "*-X" to the structural unit of the diamine containing nitrogen structure FN can be described in the structural unit (UA). In addition, the compound represented by the formula (C1-16) is a compound having "*-X 1 -W 1 " and a diamine having a vertical alignment group. 1 -W 1 The ratio of the structural unit of the diamine represented by the group represented by "*-X" to the structural unit of the diamine represented by the vertical alignment group can be applied to the description of the structural unit (UA). Similarly, the compounds represented by the formula (C1-2), formula (C1-5), formula (C1-7), formula (C1-8), formula (C1-9) and formula (C1-12) are each 1 -W 1 "The group represented by *-NR is bonded to the aromatic ring. 2 -CO- or *-CO-NR 2-partial structure of diamine. 1 -W 1 "The group represented by *-NR is bonded to the aromatic ring. 2 -CO- or *-CO-NR 2 Regarding the content ratio of the structural unit of the diamine having a partial structure of -, the description of the structural unit (UA) can be applied.
[0075] Compound represented by formula (CA-1-1)
[0076] The present invention provides a compound represented by the following formula (CA-1-1). The compound represented by the following formula (CA-1-1) is preferably used as a monomer of a polymer component contained in a liquid crystal aligning agent. The liquid crystal aligning agent can provide a liquid crystal aligning film having excellent impurity resistance, tilt imparting properties, and sealant adhesion, and can shorten the light irradiation time of the liquid crystal cell when manufacturing a PSA-type liquid crystal element.
[0077] [Chemistry 5]
[0078]
[0079] (In the formula (CA-1-1), R 8 is an alkanediyl group having 1 to 10 carbon atoms; Z 1 is an oxygen atom or -NR 9 -;R 9 is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group; R 5 and R 6 are independently monovalent substituents; r1 is an integer from 0 to 4; r2 is an integer from 0 to 5)
[0080] In the formula (CA-1-1), R 8 、R 5 、R 6 and R 9 The specific examples are as described above.
[0081] Specific examples of the compound represented by the formula (CA-1-1) include compounds represented by the formula (C1-3), formula (C1-4), and formulas (C1-14) to (C1-24).
[0082] The compound represented by the formula (CA-1-1) can be synthesized by appropriately combining conventional methods of organic chemistry. An example of a synthesis method includes synthesizing a dinitro intermediate having a nitro group in place of the primary amino group in the formula (CA-1-1), and then nitroamidating the obtained dinitro intermediate using an appropriate reduction system.
[0083] The method for synthesizing the dinitro compound can be appropriately selected depending on the target compound. For example, there are methods including reacting a hydroxyl-containing compound having a benzophenone structure with a halogenated dinitro compound, preferably in an organic solvent, in the presence of a base and, if necessary, a catalyst; reacting a hydroxyl-containing compound having a benzophenone structure with a tosyl-containing dinitro compound, preferably in an organic solvent, in the presence of a base and, if necessary, a catalyst; condensing an acid halide having a benzophenone structure with an amino-containing dinitro compound, preferably in an organic solvent, in the presence of a base and, if necessary, a catalyst; and condensing a carboxylic acid having a benzophenone structure with an amino-containing dinitro compound, preferably in an organic solvent, in the presence of a base and, if necessary, a catalyst.
[0084] The reduction reaction of the dinitro intermediate is preferably carried out in an organic solvent using catalysts such as palladium carbon, platinum oxide, zinc, iron, tin, nickel, platinum carbon, osmium carbon, etc. As the organic solvent used here, for example, ethyl acetate, toluene, tetrahydrofuran, alcohols, etc. can be enumerated. In addition, two or more of these organic solvents can also be mixed and used. Wherein, the synthetic method of the compound represented by the formula (CA-1-1) is not limited to the method.
[0085] About the structural unit (UB)
[0086] The structural unit (UB) is derived from a group having a secondary amino group, a tertiary amino group, 1 -NR 1 -* 2 and a diamine structural unit of at least one nitrogen-containing structure FN in the group consisting of a nitrogen-containing heterocyclic structure. 1 It is a monovalent leaving group. 1 "and"* 2 " represents a bond to a carbon atom excluding the carbon in the (thio)carbonyl group. It is considered that, since the liquid crystal alignment agent of the present disclosure includes a polymer having the structural unit (UB), in a liquid crystal element having a liquid crystal alignment film formed of the first liquid crystal alignment agent, the liquid crystal alignment film adsorbs impurities originating from an insulating film and the like and retains them in the film, thereby improving the effect of suppressing the intrusion of impurities into the liquid crystal layer, thereby suppressing the reduction in voltage holding ratio caused by the generation of impurities.
[0087] The diamine providing the structural unit (UB) (hereinafter also referred to as "second diamine") has * 1 -NR 1 -* 2 In the case of R 1 The thermally detachable group represented by is preferably a thermally detachable group that is detached by heat. 9 Description of the thermally detachable groups represented.
[0088] * 1 -NR 1 -* 2 The two bonds of the group represented are preferably bonded to an alkanediyl group, a substituted or unsubstituted divalent alicyclic group, or a substituted or unsubstituted divalent aromatic ring group. Among these, an alkanediyl group is preferred, and a linear alkanediyl group is more preferred, in terms of improving the sealant adhesion.
[0089] (Nitrogen-containing heterocyclic structure)
[0090] The nitrogen-containing heterocyclic ring in the nitrogen-containing heterocyclic structure may be an aromatic heterocyclic ring or an aliphatic heterocyclic ring. Furthermore, the nitrogen-containing heterocyclic ring may be a monocyclic ring or a condensed ring. Specific examples of nitrogen-containing aromatic heterocyclic rings include pyrrole rings, imidazole rings, pyrazole rings, triazole rings, pyridine rings, pyrimidine rings, pyridazine rings, quinoline rings, benzimidazole rings, carbazole rings, and pyrazine rings. Examples of nitrogen-containing aliphatic heterocyclic rings include piperidine rings, piperazine rings, morpholine rings, and hexamethyleneimine rings.
[0091] Among these, the nitrogen-containing heterocyclic ring of the second diamine is preferably at least one ring selected from the group consisting of a pyridine ring, a pyrimidine ring, a pyrazine ring, a piperidine ring, a piperazine ring, a quinoline ring, an imidazole ring, and a benzimidazole ring. From the perspective of exhibiting strong basicity, the nitrogen-containing heterocyclic ring is preferably a pyridine ring, a piperazine ring, or an imidazole ring. Furthermore, from the perspective of polymer solubility, a pyridine ring is particularly preferred. The nitrogen-containing heterocyclic ring of the second diamine may be bonded to a substituent. Examples of the substituent include an alkyl group having 1 to 3 carbon atoms.
[0092] When the structural unit (UB) has a nitrogen-containing heterocyclic ring, the polymer containing the structural unit (UB) may have a nitrogen-containing heterocyclic structure in the main chain or in a side chain. Furthermore, the polymer containing the structural unit (UB) may have a nitrogen-containing heterocyclic structure in both the main chain and the side chain. In terms of further enhancing the effect of improving impurity resistance, it is particularly preferred that the polymer containing the structural unit (UB) have a nitrogen-containing heterocyclic structure in the side chain.
[0093] Specific examples of the nitrogen-containing heterocyclic structure include partial structures represented by the following formulae (2a-1) to (2a-12).
[0094] [Chemistry 6]
[0095]
[0096] (In formulas (2a-1) to (2a-12), "*" represents a bonding bond)
[0097] In order to further improve the impurity resistance of the liquid crystal element, the diamine (second diamine) providing the structural unit (UB) preferably has a nitrogen-containing heterocyclic structure, and more preferably has at least one ring selected from the group consisting of a pyridine ring, a pyrimidine ring, a pyrazine ring, a piperidine ring, a piperazine ring, a quinoline ring, an imidazole ring, and a benzimidazole ring. Among these, the second diamine is particularly preferably a diamine capable of introducing a nitrogen-containing heterocyclic structure into the side chain of the polymer.
[0098] Specific examples of the second diamine include compounds represented by the following formulas (C2-1) to (C-29), compounds represented by the above formula (C1-14) or (C1-15), and compounds represented by formulas (C1-20) to (C1-22).
[0099] [Chemistry 7]
[0100]
[0101] [Chemistry 8]
[0102]
[0103] The structural unit (UB) may be possessed by the first polymer or the second polymer. In addition, both the first polymer and the second polymer may have the structural unit (UB). From the viewpoint of obtaining a liquid crystal element that suppresses charge accumulation when driving the liquid crystal element due to impurities in the liquid crystal element and is less likely to produce DC residual images, the first polymer preferably contains the structural unit (UA) and the structural unit (UB). In the case, the second polymer may contain the structural unit (UB) or not. In the case where the first polymer contains the structural unit (UA) and the structural unit (UB), the first polymer is preferably obtained by containing a structure derived from FN having a nitrogen-containing structure and not having "*-X 1 -W 1 " and contains the structural unit (UB) independently of the structural unit (UA).
[0104] When the first polymer includes a structural unit (UB), the content ratio of the structural unit (UB) is preferably 1 mol% or more, more preferably 5 mol% or more, and further preferably 10 mol% or more, relative to the total amount of the structural units derived from the monomers constituting the first polymer. In addition, the content ratio of the structural unit (UB) is preferably 70 mol% or less, more preferably 50 mol% or less, relative to the total amount of the structural units derived from the monomers constituting the first polymer. By setting the content ratio of the structural unit (UB) in the first polymer to within the range, a liquid crystal alignment film showing better impurity resistance can be formed, which is preferred in this respect.
[0105] The content of the structural unit (UB) in the second polymer is preferably 40 mol% or less, more preferably 20 mol% or less, relative to the total amount of structural units derived from monomers constituting the second polymer.
[0106] About the structural unit (UC)
[0107] The structural unit (UC) is introduced into the polymer component for the purpose of imparting a pretilt angle to the organic film formed using the liquid crystal aligning agent. By including a polymer having a vertical alignment group in a side chain in the liquid crystal aligning agent of the present disclosure, the tilt imparting property of the liquid crystal aligning film can be further improved.
[0108] The vertical alignment group is a group that has the function of imparting a pretilt angle to the liquid crystal alignment film. Examples of the vertical alignment group include an alkyl group having 4 to 30 carbon atoms, an alkoxy group having 4 to 30 carbon atoms, a fluoroalkyl group having 4 to 30 carbon atoms, a fluoroalkoxy group having 4 to 30 carbon atoms, a group having a structure in which a carbon chain structure having 1 to 20 carbon atoms is bonded to an alicyclic or aromatic ring, a group having a structure in which two or more rings are bonded directly or via a divalent linking group, and a group having 17 to 51 carbon atoms and a steroid skeleton.
[0109] Preferred specific examples of the vertical alignment group include groups represented by the following formula (3).
[0110] *-R 31 -R 32 -R 33 -R 34 …(3)
[0111] (In Formula 3, R 31 and R 33 are independently a single bond, a substituted or unsubstituted phenylene group, or a substituted or unsubstituted cycloalkylene group, R 32 is a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted cycloalkylene group, or -R 37 -B 31 -R 38 -(where R 37 and R 38 are independently substituted or unsubstituted phenylene or cycloalkylene, B 31 Single bond, -O-, -COO-* 4 、-OCO-* 4 、-OCH2-* 4 、-CH2O-* 4 or an alkanediyl group having 1 to 3 carbon atoms; "* 4 "Indicates that the 38 bonding bond); R 34 For hydrogen atoms, fluorine atoms, CH3COO-* 5(“* 5 "Indicates that the 33 ), an alkyl group having 1 to 20 carbon atoms, a fluoroalkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a fluoroalkoxy group having 1 to 20 carbon atoms, or a group having 17 to 51 carbon atoms and a steroid skeleton; wherein, in R 31 、R 32 and R 33 All single bonds, or R 31 、R 32 and R 33 When the total number of substituted or unsubstituted phenylene groups and substituted or unsubstituted cycloalkylene groups is 1, R 34 (alkyl group having 4 to 20 carbon atoms, fluoroalkyl group having 4 to 20 carbon atoms, alkoxy group having 4 to 20 carbon atoms, fluoroalkoxy group having 4 to 20 carbon atoms, or a group having 17 to 51 carbon atoms and a steroid skeleton; "*" indicates a bonding bond)
[0112] In the formula (3), R 34 The C1-20 alkyl group, C1-20 fluoroalkyl group, C1-20 alkoxy group, or C1-20 fluoroalkoxy group represented is preferably linear. These groups preferably have C2-20, more preferably C3-20, and even more preferably C4-20.
[0113] In R 31 、R 32 and R 33 When all are single bonds, R 34 The carbon number of is preferably 6 or more, more preferably 8 or more, and further preferably 12 or more.
[0114] As R 34 Examples of the group having 17 to 51 carbon atoms and a steroid skeleton include cholesteryl, cholesterol, and lanostanyl.
[0115] From the viewpoint of obtaining a liquid crystal element showing good liquid crystal orientation and high reliability, in the group represented by the formula (3), R 31 、R 32 and R 33 Preferably, one or both of the substituted or unsubstituted phenylene groups and the cycloalkylene groups have a total of 2 or more, and more preferably one or both of the phenylene groups and the cycloalkylene groups have a total of 2 to 4.
[0116] Specific examples of the group represented by the formula (3) include groups represented by the following formulae (3-1) to (3-12), linear alkyl groups having 8 to 30 carbon atoms, linear alkoxy groups having 8 to 30 carbon atoms, and linear fluoroalkyl groups having 8 to 30 carbon atoms.
[0117] [Chemistry 9]
[0118]
[0119] (In formulas (3-1) to (3-10), R is a fluorine atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, a fluoroalkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a fluoroalkoxy group having 1 to 20 carbon atoms; X 31 is -O-, -COO-, -OCO- or an alkanediyl group having 1 to 3 carbon atoms; "*" indicates a bonding bond)
[0120] In the case where the monomer providing the structural unit having a vertical alignment group is a diamine, the diamine having a vertical alignment group (hereinafter also referred to as the "third diamine") is preferably an aromatic diamine. The two primary amino groups in the third diamine are preferably bonded to the same aromatic ring, more preferably bonded to the same benzene ring. In the case where the third diamine has a diaminophenyl group, the bonding position of one amino group bonded to the benzene ring is not particularly limited. Specifically, 2,4-position, 2,5-position or 3,5-position can be cited relative to other groups (groups having vertical alignment groups). Among these, 2,4-position or 3,5-position is preferred.
[0121] The vertical alignment group may be directly bonded to the aromatic ring or may be bonded to the aromatic ring via a divalent linking group. Examples of the divalent linking group include: -O-, -CO-, and -COO-*. 3 、-OCO-* 3 、-NR 35 -、-NR 35 -CO-* 3 、-CO-NR 35 -* 3 , an alkanediyl group having 1 to 6 carbon atoms, a divalent group in which a hydrogen atom of an alkanediyl group having 2 to 6 carbon atoms is substituted with a hydroxyl group, -OR 36 -* 3 or -R 36 -O-* 3 (Among them, R 35 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms, R 36 is an alkanediyl group having 1 to 3 carbon atoms; 3 "Indicates that the 31 bonding bond).
[0122] The structural unit (UC) may be possessed by the first polymer or by the second polymer. In addition, both the first polymer and the second polymer may have the structural unit (UC). From the viewpoint of imparting a desired pretilt angle to the organic film formed using the liquid crystal alignment agent by irradiating the organic film with as little light as possible, the first polymer preferably comprises the structural unit (UA) and the structural unit (UC). In the case described, the second polymer may or may not comprise the structural unit (UC). In the case where the first polymer comprises the structural unit (UA) and the structural unit (UC), the first polymer is preferably obtained by comprising a structural unit derived from a vertical alignment group and not having "*-X 1 -W 1 " and contains the structural unit (UC) independently of the structural unit (UA).
[0123] When the first polymer contains the structural unit (UC), the content of the structural unit (UC) is preferably 1 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, relative to the total amount of the structural units derived from the monomers constituting the first polymer. Furthermore, the content of the structural unit (UC) is preferably 50 mol% or less, more preferably 30 mol% or less, relative to the total amount of the structural units derived from the monomers constituting the first polymer.
[0124] When the second polymer contains the structural unit (UC), the content of the structural unit (UC) is preferably 0.5 mol% or more, more preferably 1 mol% or more, and even more preferably 2 mol% or more, relative to the total amount of the structural units derived from the monomers constituting the second polymer. Furthermore, the content of the structural unit (UC) is preferably 30 mol% or less, more preferably 20 mol% or less, relative to the total amount of the structural units derived from the monomers constituting the second polymer.
[0125] About structural units (UD)
[0126] The structural unit (UD) is derived from a *-NR having an aromatic ring and bonding to the aromatic ring. 2 -CO- or *-CO-NR 2 -(where R 2 A structural unit of a diamine (hereinafter also referred to as "fourth diamine") containing a hydrogen atom or a monovalent organic group, and "*" represents a bond to an aromatic ring. By introducing the structural unit (UD) into the polymer, a *-NR is bonded to the aromatic ring. 2 -CO- or *-CO-NR 2 The partial structure of - is introduced into the polymer. By making the liquid crystal aligning agent contain the polymer containing the structural unit (UD) having such a partial structure, the effect of suppressing the charge accumulation of the liquid crystal element can be further improved.
[0127] In the fourth diamine, *-NR 2 -CO- or *-CO-NR 2 - The aromatic ring to which the bond is attached may be an aromatic hydrocarbon ring or an aromatic heterocyclic ring. Of these, a benzene ring, a naphthalene ring, a pyridine ring or a pyrimidine ring is preferred. *-NR 2 -CO- or *-CO-NR 2 The aromatic ring to which - is bonded may further have a substituent. Examples of the substituent include an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a halogen atom, and a hydroxyl group.
[0128] As R 2 The monovalent organic group represented by can be an alkyl group having 1 to 5 carbon atoms and a monovalent leaving group. Specific examples and preferred examples of the monovalent leaving group include the group having R in the second diamine. 1 The same group as that shown in the description of the leaving group represented by R 2 It is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group. 2 -CO- or *-CO-NR 2 - may also form part of the urea bond.
[0129] There will be *-NR bonded to the aromatic ring 2 -CO- or *-CO-NR 2 -When part or all of the partial structure of the fourth diamine is introduced into the side chain of the polymer, specific examples of the fourth diamine include: compounds represented by the above formula (C1-2), formula (C1-5), formula (C1-7), formula (C1-8), formula (C1-9), formula (C2-11), formula (C2-12), formula (C2-15), formula (C2-17), formula (C2-19) and formula (C2-29), and vertical alignment groups are introduced through *-NR 2 -CO- or *-CO-NR 2 - and compounds bonded to diaminophenyl, etc.
[0130] There will be *-NR bonded to the aromatic ring 2 -CO- or *-CO-NR 2 When a partial structure of - is introduced into the main chain of the polymer, the fourth diamine is preferably an aromatic diamine, and specifically, a compound represented by the following formula (4) is preferred.
[0131] [Chemistry 10]
[0132]
[0133] (In formula (4), X 41and X 42 Independently of each other *-NR 2 -CO- or *-CO-NR 2 -; "*" indicates the bond to the benzene ring; X 43 and X 44 are independently a single bond or -NR 43 -;R 43 is a hydrogen atom or a monovalent organic group; R 40 A divalent hydrocarbon group or a hydrocarbon group containing -O-, -S-, -NR between carbon-carbon bonds 44 -、-NR 44 -CO- or -NR 44 -CO-NR 45 -divalent radical; R 44 and R 45 are independently a hydrogen atom or a monovalent organic group; R 41 and R 42 are independently monovalent substituents; m1 is an integer from 0 to 3; m2 and m3 are independently integers from 0 to 4; when m1 is 2 or more, multiple R 40 Same or different, multiple X 44 Same or different, multiple X 42 Same or Different)
[0134] In the formula (4), R 40 The divalent hydrocarbon group represented by is preferably an aliphatic hydrocarbon group, more preferably an alkanediyl group. 40 The carbon number of the divalent hydrocarbon group represented is preferably 1-20, more preferably 1-10.
[0135] About R 43 、R 44 or R 45 Specific examples and preferred examples of the monovalent organic group represented by include the following: 2 The same groups as those shown in the description of the monovalent organic group represented by R 43 、R 44 or R 45 Each of them is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group.
[0136] There will be *-NR bonded to the aromatic ring 2 -CO- or *-CO-NR 2 When a partial structure of - is introduced into the main chain of the polymer, specific examples of the fourth diamine include compounds represented by the following formula (C4-1) to formula (C4-9).
[0137] [Chemistry 11]
[0138]
[0139] When the first polymer contains the structural unit (UD), the content of the structural unit (UD) is preferably 2 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, relative to the total amount of the structural units derived from the monomers constituting the first polymer. Furthermore, the content of the structural unit (UD) is preferably 75 mol% or less, more preferably 55 mol% or less, and even more preferably 45 mol% or less, relative to the total amount of the structural units derived from the monomers constituting the first polymer.
[0140] Furthermore, when the second polymer contains structural units (UD), the content of the structural units (UD) relative to the total amount of structural units derived from monomers constituting the second polymer is preferably 2 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more. Furthermore, the content of the structural units (UD) relative to the total amount of structural units derived from monomers constituting the second polymer is preferably 75 mol% or less, more preferably 55 mol% or less, and even more preferably 45 mol% or less.
[0141] The first polymer and the second polymer may also contain structural units derived from a diamine (hereinafter also referred to as a "fifth diamine") that is different from the first diamine, the second diamine, the third diamine, and the fourth diamine. Examples of the fifth diamine include aliphatic diamines (chain diamines, alicyclic diamines), aromatic diamines, and diaminoorganosiloxanes.
[0142] Specific examples of these include meta-xylylenediamine, 1,3-propylenediamine, tetramethylenediamine, pentamethylenediamine, and hexamethylenediamine; and alicyclic diamines include 1,4-diaminocyclohexane and 4,4'-methylenebis(cyclohexylamine).
[0143] Examples of the aromatic diamine include p-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenyl ether, 4-aminophenyl-4-aminobenzoate, 4,4'-diaminoazobenzene, 3,5-diaminobenzoic acid, 1,5-bis(4-aminophenoxy)pentane, 1,2-bis(4-aminophenoxy)ethane, 1,3-bis(4-aminophenoxy) Propane, 1,6-bis(4-aminophenoxy)hexane, bis[2-(4-aminophenyl)ethyl]adipic acid, 1,4-bis(4-aminophenyl)-piperazine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(4-aminophenyl)hexafluoropropane, 4, 4'-(phenylenediisopropylidene)dianiline, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-[4,4'-propane-1,3-diylbis(piperidin-1,4-diyl)]diphenylamine, 4,4'-diaminobenzanilide, 4,4'-diaminostilbene, 1,4-bis(4-aminophenyl)-piperazine, bis[2-(4-aminophenyl)] 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, etc.
[0144] Examples of the diaminoorganosiloxane include 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, and other diamines described in JP-A-2010-97188 may also be used.
[0145] In the first polymer, the content ratio of the structural units derived from the fifth diamine relative to the total amount of the structural units derived from the monomers constituting the first polymer is preferably 80 mol% or less, and more preferably 70 mol% or less. Furthermore, in the second polymer, the content ratio of the structural units derived from the fifth diamine relative to the total amount of the structural units derived from the monomers constituting the second polymer is preferably 99 mol% or less, and more preferably 95 mol% or less.
[0146] The first polymer and the second polymer, when at least one selected from the group consisting of polyamic acid and polyimide, can be obtained by a method comprising reacting tetracarboxylic dianhydride with a diamine (polycondensation reaction). The first polymer and the second polymer thus obtained contain structural units derived from tetracarboxylic dianhydride and structural units derived from a diamine compound.
[0147] Tetracarboxylic dianhydride
[0148] As tetracarboxylic dianhydride, aliphatic tetracarboxylic dianhydride and aromatic tetracarboxylic dianhydride are mentioned, for example. Aliphatic tetracarboxylic dianhydride contains chain tetracarboxylic dianhydride and alicyclic tetracarboxylic dianhydride.
[0149] Specific examples of these include chain tetracarboxylic dianhydrides such as 1,2,3,4-butanetetracarboxylic dianhydride;
[0150] Examples of the alicyclic tetracarboxylic dianhydride include 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 2,4,6,8-tetracarboxybicyclo[3.3.0]octane-2:4,6:8-dianhydride, cyclopentanetetracarboxylic dianhydride, and cyclohexanetetracarboxylic dianhydride.
[0151] Examples of the aromatic tetracarboxylic dianhydride include pyromellitic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, ethylene glycol ditrimellitic anhydride, 4,4'-carbonyldiphthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and 3,3',4,4'-diphenylethertetracarboxylic dianhydride. Furthermore, the tetracarboxylic dianhydride described in Japanese Patent Application Laid-Open No. 2010-97188 can be used as the tetracarboxylic dianhydride.
[0152] When the second polymer is at least one selected from the group consisting of polyamic acid and polyimide, the content ratio of the structural units derived from aromatic tetracarboxylic dianhydride in the second polymer is preferably 50 mol% or less relative to the total amount of the structural units derived from tetracarboxylic dianhydride constituting the second polymer. If the proportion of the structural units derived from aromatic tetracarboxylic dianhydride constituting the second polymer is high, there is a tendency for impurity resistance to decrease. In order to obtain a liquid crystal cell with excellent impurity resistance, the proportion of the structural units derived from aromatic tetracarboxylic dianhydride constituting the second polymer relative to the total amount of the structural units derived from tetracarboxylic dianhydride constituting the second polymer is more preferably 40 mol% or less, further preferably 30 mol% or less, and further more preferably 20 mol% or less.
[0153] When the first polymer is at least one selected from the group consisting of polyamic acid and polyimide, the tetracarboxylic dianhydride constituting the first polymer preferably comprises an aliphatic tetracarboxylic dianhydride, from the perspectives of improving the solubility of the polymer and obtaining a liquid crystal device exhibiting favorable electrical properties. Specifically, the proportion of the structural units derived from the aliphatic tetracarboxylic dianhydride constituting the first polymer relative to the total amount of the structural units derived from the tetracarboxylic dianhydride constituting the first polymer is more preferably 50 mol% or more, further preferably 70 mol% or more, and even more preferably 80 mol% or more.
[0154] Next, methods for producing polyamic acid, polyimide, polyorganosiloxane, and addition polymer will be described.
[0155] Synthesis of polyamic acid
[0156] Polyamic acid can be obtained by reacting the tetracarboxylic dianhydride as described above with a diamine compound and an optional molecular weight modifier. The ratio of the tetracarboxylic dianhydride and the diamine compound used in the synthesis reaction of polyamic acid is preferably such that the anhydride group of the tetracarboxylic dianhydride is 0.2 to 2 equivalents relative to 1 equivalent of the amino group of the diamine compound. As molecular weight modifiers, for example, monoanhydrides such as maleic anhydride, phthalic anhydride, and itaconic anhydride; monoamine compounds such as aniline, cyclohexylamine, and n-butylamine; monoisocyanate compounds such as phenyl isocyanate and naphthyl isocyanate; etc. The ratio of the molecular weight modifier used is preferably set to 20 parts by mass or less relative to a total of 100 parts by mass of the tetracarboxylic dianhydride and the diamine compound used.
[0157] The synthesis reaction of polyamic acid is preferably carried out in an organic solvent. The reaction temperature at this time is preferably -20°C to 150°C, and the reaction time is preferably 0.1 hour to 24 hours. As the organic solvent used in the reaction, for example, there can be mentioned: aprotic polar solvents, phenolic solvents, alcohols, ketones, esters, ethers, halogenated hydrocarbons, hydrocarbons, etc. Particularly preferred organic solvents are preferably selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, tetramethylurea, hexamethylphosphoric triamide, metacresol, xylenol and halogenated phenol as solvents, or a mixture of one or more of them and other organic solvents (for example, butyl cellosolve, diethylene glycol diethyl ether, etc.). The amount (a) of the organic solvent used is preferably set to an amount that makes the total amount (b) of tetracarboxylic dianhydride and diamine 0.1% by mass to 50% by mass relative to the total amount (a+b) of the reaction solution.
[0158] In this manner, a reaction solution in which polyamic acid is dissolved is obtained. The reaction solution may be used directly for the preparation of a liquid crystal aligning agent, or the polyamic acid contained in the reaction solution may be separated and then used for the preparation of a liquid crystal aligning agent.
[0159] Synthesis of polyimide
[0160] Polyimides can be obtained, for example, by dehydrating and ring-closing polyamic acid and then imidizing it. The imidization ratio of the polyimide is preferably 20% to 90%, more preferably 30% to 85%. The imidization ratio is expressed as a percentage of the number of imide ring structures relative to the total number of amic acid structures and imide ring structures in the polyimide.
[0161] The dehydration ring-closure of polyamic acid is preferably carried out by the following method: polyamic acid is dissolved in an organic solvent, a dehydrating agent and a dehydration ring-closure catalyst are added to the solution, and heating is performed as needed. In the method, as a dehydrating agent, for example, anhydrides such as acetic anhydride, propionic anhydride, and trifluoroacetic anhydride can be used. Relative to 1 mol of the amic acid structure of polyamic acid, the amount of the dehydrating agent used is preferably set to 0.01 mol to 20 mol. As a dehydration ring-closure catalyst, for example, tertiary amines such as pyridine, collidine, dimethylpyridine, and triethylamine can be used. Relative to 1 mol of the dehydrating agent used, the amount of the dehydration ring-closure catalyst used is preferably set to 0.01 mol to 10 mol.
[0162] As the organic solvent used in the dehydration ring-closure reaction, the organic solvents exemplified as the organic solvents used in the synthesis of polyamic acid can be cited. The reaction temperature of the dehydration ring-closure reaction is preferably 0°C to 180°C. The reaction time is preferably 1.0 hour to 120 hours. In addition, the reaction solution containing the polyimide can be directly used in the preparation of the liquid crystal alignment agent. In addition, the polyimide can also be separated from the reaction solution, and the separated polyimide can be used in the preparation of the liquid crystal alignment agent.
[0163] Synthesis of polyorganosiloxane
[0164] Polyorganosiloxane can be obtained, for example, by hydrolyzing and condensing a hydrolyzable silane compound. Examples of the hydrolyzable silane compound include alkoxysilane compounds such as tetramethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and dimethyldiethoxysilane; nitrogen- and sulfur-containing alkoxysilane compounds such as 3-mercaptopropyltriethoxysilane, mercaptomethyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-(3-cyclohexylamino)propyltrimethoxysilane; 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, and 3-aminopropyltrimethoxysilane. Silane compounds containing epoxy groups, such as silane, 3-glycidyloxypropylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane; alkoxysilane compounds containing unsaturated bonds, such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltriethoxysilane, and p-phenyleneditrimethoxysilane; and trimethoxysilylpropylsuccinic anhydride. Hydrolyzable silane compounds may be used alone or in combination of two or more. Furthermore, the term "(meth)acryloxy" encompasses both "acryloxy" and "methacryloxy."
[0165] The hydrolysis / condensation reaction can be carried out by reacting one or more of the silane compounds described above with water, preferably in the presence of a suitable catalyst and an organic solvent. When the reaction is carried out, the ratio of water used is preferably 1 to 30 moles relative to 1 mole of the silane compound (total amount). As the catalyst used, for example, there can be mentioned: acid, alkali metal compound, organic base, titanium compound, zirconium compound, etc. The amount of the catalyst used varies according to the reaction conditions such as the type of catalyst and temperature, and should be appropriately set. For example, it is preferably 0.01 times mole to 3 times mole relative to the total amount of the silane compound. As the organic solvent used, for example, there can be mentioned: hydrocarbons, ketones, esters, ethers, alcohols, etc. Among these, it is preferred to use a water-insoluble or poorly water-soluble organic solvent. The ratio of the organic solvent used is preferably 10 to 10,000 parts by mass relative to a total of 100 parts by mass of the silane compound used in the reaction.
[0166] The hydrolysis / condensation reaction is preferably carried out by heating in an oil bath, for example. The heating temperature is preferably set to 130°C or less, and the heating time is preferably set to 0.5 to 12 hours. After the reaction is completed, the organic solvent layer separated from the reaction solution is dried using a desiccant, if necessary, and the solvent is removed to obtain the target polyorganosiloxane. The synthesis method of the polyorganosiloxane is not limited to the hydrolysis / condensation reaction described above; for example, the reaction can be carried out by reacting a hydrolyzable silane compound in the presence of oxalic acid and an alcohol.
[0167] When using a nitrogen-containing structure FN, a vertical alignment group or a *-NR bonded to an aromatic ring 2 -CO- or *-CO-NR 2 In the case of a polyorganosiloxane having a partial structure of - as the second polymer, a polyorganosiloxane having an epoxy group in the side chain can be obtained by the above polymerization, and then a polyorganosiloxane having a nitrogen-containing structure FN, a vertical alignment group or a *-NR bonded to the aromatic ring can be obtained. 2 -CO- or *-CO-NR 2 -, thereby obtaining the polyorganosiloxane. The reaction of the epoxy-containing polyorganosiloxane with the carboxylic acid is preferably carried out in the presence of a catalyst (e.g., a tertiary organic amine or a quaternary organic amine, a quaternary ammonium salt, etc.) and an organic solvent. After the reaction is completed, the organic solvent layer separated from the reaction solution is preferably washed with water. After washing, the organic solvent layer is dried using an appropriate desiccant as needed, and the solvent is removed to obtain the polyorganosiloxane as the target product.
[0168] Synthesis of addition polymers
[0169] Addition polymers can be obtained by polymerizing one or more monomers having polymerizable carbon-carbon unsaturated bonds. Specific examples of addition polymers include styrene-based polymers, maleimide-based polymers, styrene-maleimide-based polymers, and (meth)acrylic acid-based polymers.
[0170] As the monomer constituting the addition polymer, any monomer having a polymerizable unsaturated bond can be used. Examples of such monomers include compounds having a (meth)acryloyl group, a vinyl group, a vinylphenyl group, a maleimide group, and the like.
[0171] Specific examples of monomers constituting the addition polymer include unsaturated carboxylic acids such as (meth)acrylic acid, α-ethylacrylic acid, maleic acid, fumaric acid, and vinylbenzoic acid; unsaturated carboxylic acid esters such as alkyl (meth)acrylates (e.g., methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc.), cycloalkyl (meth)acrylates, benzyl (meth)acrylate, trimethoxysilylpropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxybutyl (meth)acrylate, and 4-hydroxybutyl glycidyl (meth)acrylate; and (meth)acrylic compounds such as unsaturated polycarboxylic acid anhydrides such as maleic anhydride.
[0172] Aromatic vinyl compounds such as styrene, methylstyrene, divinylbenzene and 4-(glycidyloxymethyl)styrene; conjugated diene compounds such as 1,3-butadiene and 2-methyl-1,3-butadiene;
[0173] Maleimide compounds such as N-methylmaleimide, N-cyclohexylmaleimide, N-phenylmaleimide, 4-(2,5-dioxo-3-pyrrolin-1-yl)benzoic acid, N-(4-glycidyloxyphenyl)maleimide, N-glycidylmaleimide, 3-maleimidobenzoic acid, 3-maleimidopropionic acid, 3-(2,5-dioxo-3-pyrrolin-1-yl)benzoic acid, and methyl 4-(2,5-dioxo-3-pyrrolin-1-yl)benzoate. Furthermore, compounds having a vertical alignment group may be used as monomers constituting the addition polymer.
[0174] The addition polymer can be obtained, for example, by polymerizing the monomer in the presence of a polymerization initiator. As the polymerization initiator used, for example, azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) are preferred. The proportion of the polymerization initiator used is preferably 0.01 to 30 parts by mass relative to 100 parts by mass of all monomers used in the reaction. The polymerization reaction is preferably carried out in an organic solvent. As the organic solvent used in the reaction, for example, alcohols, ethers, ketones, amides, esters, hydrocarbon compounds, etc. are listed, preferably diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether acetate, etc. The reaction temperature is preferably 30°C to 120°C, and the reaction time is preferably 1 to 36 hours. The amount (a) of the organic solvent used is preferably such that the total amount (b) of the monomers used in the reaction is 0.1% to 60% by mass relative to the total amount (a+b) of the reaction solution.
[0175] From the perspective of making the tilt imparting property of the liquid crystal alignment film and the sealing material adhesion better, the second polymer preferably has at least one functional group selected from the group consisting of a carboxyl group, an epoxy group and a hydroxyl group. Here, as the polymer having a carboxyl group, at least one selected from the group consisting of polyamic acid and polyimide can be preferably used. In addition, an addition polymer containing a structural unit derived from a monomer having a carboxyl group can also be used. As the polymer having an epoxy group, at least one selected from the group consisting of polyorganosiloxane and an addition polymer can be preferably used. As the polymer having a hydroxyl group, at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane and an addition polymer can be preferably used.
[0176] From the perspective of further improving the tilt-imparting properties, impurity resistance, and sealant adhesion of the liquid crystal alignment film, the second polymer preferably includes a structural unit having at least one functional group selected from the group consisting of a carboxyl group, an epoxy group, and a hydroxyl group. In the second polymer, the content of the structural unit having at least one functional group selected from the group consisting of a carboxyl group, an epoxy group, and a hydroxyl group is preferably 1 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, relative to the total amount of structural units derived from monomers constituting the second polymer.
[0177] Regarding the solution viscosity of each of the first polymer and the second polymer, when prepared as a 10% by mass solution, the polymer preferably has a solution viscosity of 10 mPa·s to 800 mPa·s, and more preferably has a solution viscosity of 15 mPa·s to 500 mPa·s. The solution viscosity (mPa·s) is a value measured at 25°C using an E-type rotational viscometer on a 10% by mass solution of the polymer prepared in a good solvent for the polymer (e.g., γ-butyrolactone, N-methyl-2-pyrrolidone, etc.).
[0178] The first polymer and the second polymer each have a polystyrene-equivalent weight average molecular weight (Mw) as measured by gel permeation chromatography (GPC) of preferably 1,000 to 500,000, more preferably 2,000 to 300,000. The molecular weight distribution (Mw / Mn), represented by the ratio of Mw to the polystyrene-equivalent number average molecular weight (Mn) as measured by GPC, is preferably 7 or less, more preferably 5 or less.
[0179] For example, when the first polymer and the second polymer contained in the liquid crystal aligning agent are polyamic acid, the following [Aspect 1B] to [Aspect 3B] can be mentioned as preferred specific aspects of the combination of the first polymer and the second polymer.
[0180] [Aspect 1B] Aspects in which the first polymer is a polyamic acid containing structural units (UA), (UB), and (UC), and the second polymer is a polyamic acid containing structural units (UB) instead of (UA).
[0181] [Aspect 2B] Aspects in which the first polymer is a polyamic acid containing the structural unit (UA), the structural unit (UB), and the structural unit (UC), and the second polymer is a polyamic acid not containing the structural unit (UA) and the structural unit (UB).
[0182] [Aspect 3B] Aspects in which the first polymer is a polyamic acid containing structural units (UA), (UB), and (UC), and the second polymer is a polyamic acid containing structural units (UC) instead of (UA).
[0183] In these aspects, the structural unit (UB) is preferably a structural unit different from the structural unit (UA), and the structural unit (UC) is preferably a structural unit different from the structural unit (UA).
[0184] Relative to the total amount of 100 parts by mass of the first polymer and the second polymer, the content of the first polymer in the liquid crystal alignment agent is preferably 5 parts by mass or more, more preferably 10 parts by mass or more. In addition, relative to the total amount of 100 parts by mass of the first polymer and the second polymer, the content of the first polymer is preferably 70 parts by mass or less, more preferably 60 parts by mass or less, and further preferably 55 parts by mass or less. In addition, relative to the total amount of 100 parts by mass of the first polymer and the second polymer, the content of the second polymer is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and further preferably 45 parts by mass or more. In addition, relative to the total amount of 100 parts by mass of the first polymer and the second polymer, the content of the second polymer is preferably 95 parts by mass or less, more preferably 90 parts by mass or less. By setting the contents of the first polymer and the second polymer to be within the range respectively, good tilt imparting properties can be ensured, and the shortening of the light irradiation time for consuming the photopolymerizable compound when manufacturing the PSA type liquid crystal element is achieved, and a liquid crystal alignment film having excellent impurity resistance is obtained.
[0185] <Other ingredients>
[0186] The liquid crystal aligning agent may further contain a component (other component) different from the first polymer and the second polymer as needed, in addition to the first polymer and the second polymer.
[0187] Other polymers
[0188] The liquid crystal alignment agent of the present disclosure may also contain a polymer (other polymer) different from the first polymer and the second polymer. As other polymers, for example, polymers having a main skeleton of polyester, polyurea, cellulose derivatives or polyacetal can be listed. With respect to 100 parts by mass of the total amount of solid components contained in the liquid crystal alignment agent, the content of other polymers in the liquid crystal alignment agent is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and further preferably 5 parts by mass or less.
[0189] Cross-linking agent
[0190] The liquid crystal alignment agent of the present disclosure may also contain a crosslinking agent. Examples of the crosslinking agent include a group selected from a group having a polymerizable carbon-carbon bond, a cyclic ether group, a cyclic thioether group, an isocyanate group, a protected isocyanate group, a hydroxymethyl group, a protected hydroxymethyl group, a hydroxyalkylamide group, a protected hydroxyalkylamide group, a cyclic carbonate group, a group "-CR 90 =CR 91 -R 92 -”(where R 90 is a monovalent organic group that is released by reaction with an amino group; R 91 is a hydrogen atom or an alkyl group, R 92 (electron-withdrawing group), a compound containing at least one crosslinking group selected from the group consisting of a silanol group, an amino group, a protected amino group and an alkoxysilyl group.
[0191] Among the crosslinkable groups, examples of the group having a polymerizable carbon-carbon bond include a (meth)acryloyl group, a maleimide group, an alkenyl group, a vinylphenyl group, a vinyl ether group, and a 3-methylenetetrahydrofuran-2(3H)-one-5-yl group.
[0192] From the perspective of impurity resistance (particularly, reduction in DC sticking), compounds having a functional group reactive with an amino group or a carboxyl group are preferably used as crosslinking agents among the above. Among these, compounds having a total of two or more of at least one selected from the group consisting of a cyclic ether group, a hydroxyalkylamide group, a protected hydroxyalkylamide group, a hydroxymethyl group, a protected hydroxymethyl group, a protected isocyanate group, an amino group, a protected amino group, and an alkoxysilyl group are preferably used per molecule.
[0193] From the perspective of achieving a well-balanced improvement in the liquid crystal orientation, electrical properties, and sealant adhesion of the liquid crystal element, the number of crosslinkable groups contained in one molecule of the crosslinking agent is preferably 2 to 12, more preferably 2 to 8. From the perspective of ensuring good storage stability, the molecular weight of the crosslinking agent is preferably 1,200 or less, more preferably 1,000 or less, and even more preferably 800 or less.
[0194] Specific examples of crosslinking agents include compounds having a cyclic ether group, such as N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenyl ether, N,N-diglycidyl-aminomethylcyclohexane, N,N-diglycidyl-cyclohexylamine, cyclic siloxanes having two or more glycidyl groups, and peroxidative epoxidation products of pentaerythritol tetraallyl ether.
[0195] Examples of the compound having a hydroxyalkylamide group or a protected hydroxyalkylamide group include compounds represented by the following formulas (c-1) to (c-3);
[0196] Examples of the compound having a hydroxymethyl group or a protected hydroxymethyl group include compounds represented by the following formulas (c-4) to (c-9);
[0197] Examples of the compound having a protected isocyanate group include compounds represented by the following formulas (c-10) to (c-14);
[0198] Examples of the compound having an amino group or a protected amino group include compounds represented by the following formulae (c-15) to (c-19).
[0199] [Chemistry 12]
[0200]
[0201] [Chemistry 13]
[0202]
[0203] (In formula (c-8), Ac is an acetyl group)
[0204] [Chemistry 14]
[0205]
[0206] (In formula (c-10) and formula (c-11), R 93 is tert-butoxy)
[0207] [Chemistry 15]
[0208]
[0209] In the case of a cross-linking agent being deployed in the liquid crystal alignment agent of the present disclosure, with respect to the viewpoint of improving the liquid crystal orientation of liquid crystal cell and the sealant adhesion of electrical properties and liquid crystal alignment film in a balanced manner, relative to the total amount of the polymer components contained in the liquid crystal alignment agent (that is, the total amount of the first polymer, the second polymer and other polymers) 100 parts by mass, the content of the cross-linking agent in the liquid crystal alignment agent is preferably more than 0.5 parts by mass. Relative to the total amount 100 parts by mass of polymer components, the content of the cross-linking agent is more preferably more than 1 part by mass, and further preferably more than 2 parts by mass. In addition, relative to the total amount 100 parts by mass of polymer components, the content of the cross-linking agent is preferably less than 30 parts by mass, more preferably less than 20 parts by mass.
[0210] Solvent
[0211] The liquid crystal alignment agent disclosed herein is prepared in the form of a liquid composition, wherein the liquid composition is prepared by dispersing or dissolving the first polymer, the second polymer, and other components used as needed in an appropriate solvent.
[0212] As the solvent, an organic solvent can be preferably used. Specific examples thereof include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,2-dimethyl-2-imidazolidinone, 1,3-dimethyl-2-imidazolidinone, phenol, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone, diacetone alcohol, 1-hexanol, 2-hexanol, propane-1,2-diol, 3-methoxy-1-butanol, ethylene glycol monomethyl ether, methyl lactate, ethyl lactate, butyl lactate, methyl acetate, ethyl acetate, butyl acetate, ethyl acetate, methyl ... The solvents include methyl methoxypropionate, ethyl acetoacetate, ethyl propionate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol n-propyl ether, ethylene glycol isopropyl ether, ethylene glycol n-butyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisoamyl ether, ethylene carbonate, propylene carbonate, propylene glycol monomethyl ether (PGME), diethylene glycol diethyl ether acetate, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol diacetate, cyclopentanone, and cyclohexanone. One solvent may be used alone or two or more solvents may be used in combination.
[0213] Other components contained in the liquid crystal alignment agent include, in addition to those mentioned above, antioxidants, metal chelate compounds, curing accelerators, surfactants, fillers, dispersants, photosensitizers, etc. The proportions of other components can be appropriately selected according to the compound within the range that does not impair the effects of the present disclosure.
[0214] The solid content concentration of the liquid crystal alignment agent (the ratio of the total mass of the components of the liquid crystal alignment agent other than the solvent to the total mass of the liquid crystal alignment agent) can be appropriately selected considering viscosity, volatility, etc., preferably in the range of 1% by mass to 10% by mass. If the solid content concentration is 1% by mass or more, the film thickness of the coating can be fully ensured, and a liquid crystal alignment film showing a better liquid crystal orientation can be obtained, which is preferred in this respect. On the other hand, if the solid content concentration is 10% by mass or less, there is a tendency that the coating can be set to a moderate thickness, and a liquid crystal alignment film showing a good liquid crystal orientation can be easily obtained. In addition, there is a tendency that the viscosity of the liquid crystal alignment agent becomes moderate, which can make the coating property good.
[0215] Second liquid crystal alignment agent
[0216] The second liquid crystal alignment agent of the present disclosure contains the first polymer and a cross-linking agent. The description of the first liquid crystal alignment agent can be applied to the details of the type or content of the first polymer and the cross-linking agent. Furthermore, the second liquid crystal alignment agent may also contain components such as the solvent in addition to the first polymer and the cross-linking agent. The second liquid crystal alignment agent is the same as the first liquid crystal alignment agent except that it does not contain the second polymer.
[0217] Liquid crystal alignment film and liquid crystal element
[0218] The liquid crystal alignment film of the present invention can be formed by a liquid crystal alignment agent prepared in the manner described. In addition, the liquid crystal element of the present invention includes a liquid crystal alignment film formed using the liquid crystal alignment agent described in the above. The action mode of the liquid crystal in the liquid crystal element is not particularly limited, for example, it can be applied to various modes such as twisted nematic (TN) type, super twisted nematic (STN) type, vertical alignment (VA) type (including vertical alignment-multi-domain vertical alignment (VA-MVA) type, vertical alignment-patterned vertical alignment (VA-PVA) type, etc.), in-plane switching (IPS) type, fringe field switching (FFS) type, optically compensated bend (OCB) type, polymer stabilized alignment (PSA) type, etc. The liquid crystal element can be produced, for example, by a method including the following steps 1 to 3. In step 1, the substrate used varies depending on the desired operation mode. Steps 2 and 3 are common to each operation mode.
[0219] (Step 1: Formation of coating film)
[0220] First, a liquid crystal alignment agent is applied to a substrate, and the applied surface is preferably heated to form a coating film on the substrate. As a substrate, for example, a transparent substrate comprising the following materials can be used: glass such as float glass and soda glass; plastics such as polyethylene terephthalate, polybutylene terephthalate, polyethersulfone, polycarbonate, and poly(alicyclic olefin). As a transparent conductive film provided on one side of the substrate, a NESA film (a registered trademark of PPG Corporation, USA) comprising tin oxide (SnO2) or an indium tin oxide (ITO) film comprising indium oxide-tin oxide (In2O3-SnO2) can be used. When manufacturing a TN type, STN type, VA type, or PSA type liquid crystal cell, two substrates provided with patterned transparent conductive films are used. On the other hand, when manufacturing an IPS type or FFS type liquid crystal cell, a substrate provided with electrodes and an opposing substrate without electrodes are used, wherein the electrodes comprise a transparent conductive film or a metal film patterned into a comb shape. As the metal film, for example, a film containing a metal such as chromium can be used. The liquid crystal aligning agent is preferably applied to the substrate by offset printing, spin coating, roll coater coating, or inkjet printing on the electrode formation surface.
[0221] After applying the liquid crystal alignment agent, it is preferred to implement preheating (pre-baking) for the purpose of preventing the applied liquid crystal alignment agent from sagging. The pre-baking temperature is preferably 30°C to 200°C, and the pre-baking time is preferably 0.25 minutes to 10 minutes. Thereafter, as needed, a calcination (post-baking) process is implemented for the purpose of completely removing the solvent or thermally imidizing the amide structure present in the polymer. The calcination temperature (post-baking temperature) at this time is preferably 80°C to 300°C, and the post-baking time is preferably 5 minutes to 200 minutes. The film thickness of the film thus formed is preferably 0.001μm to 1μm. After applying the liquid crystal alignment agent on the substrate, the organic solvent is removed to form a liquid crystal alignment film or a coating film of the liquid crystal alignment film.
[0222] (Step 2: Orientation Treatment)
[0223] In the case of manufacturing the liquid crystal cell of TN type, STN type, IPS type or FFS type, the process (orientation treatment) of giving liquid crystal orientation ability to the coating film formed in operation 1 is implemented. Thus, the orientation ability of liquid crystal molecules is given to the coating film and becomes a liquid crystal alignment film. As orientation treatment, a friction treatment in which the surface of the coating film formed on the substrate is rubbed by cotton (cotton) and the light orientation treatment in which the coating film is irradiated with light and the liquid crystal orientation ability is given can be listed. On the other hand, in the case of manufacturing the liquid crystal cell of vertical alignment type (VA type), the coating film formed in operation 1 can be directly used as a liquid crystal alignment film, but orientation treatment can also be implemented to the coating film. The preferred liquid crystal alignment film for the liquid crystal cell of vertical alignment type can also be preferably used for the liquid crystal cell of PSA type. In the case of manufacturing PSA type liquid crystal cell, pretilt angle can be given by friction treatment.
[0224] The light irradiation in the photo-alignment treatment can be performed by the following methods, etc.: a method of irradiating the coating film after the post-baking process; a method of irradiating the coating film after the pre-baking process and before the post-baking process; a method of irradiating the coating film during the heating process of the coating film in at least any one of the pre-baking process and the post-baking process. In the photo-alignment treatment, as the radiation irradiated to the coating film, for example, ultraviolet rays and visible light containing light with a wavelength of 150nm to 800nm can be used. Preferably, ultraviolet rays containing light with a wavelength of 200nm to 400nm are used. When the radiation is polarized, it can be linearly polarized or partially polarized. In addition, when the radiation used is linearly polarized or partially polarized, the irradiation can be performed from a direction perpendicular to the substrate surface, from an oblique direction, or a combination of these directions. When irradiating non-polarized radiation, the irradiation direction is set to an oblique direction.
[0225] As the light source used, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. The radiation dose is preferably 400 J / m 2 ~20,000J / m 2 , more preferably 1,000 J / m 2 ~5,000J / m 2 In order to improve the reactivity, the coating film may be irradiated with light while being heated.
[0226] When manufacturing the liquid crystal alignment film, the coating film to which the light irradiation treatment has been implemented can be heated in a temperature range of more than 120°C and less than 280°C, thereby further improving the liquid crystal orientation (heating rearrangement). The heating may be post-baking, or it may be a heat treatment performed after post-baking independently of post-baking. When the coating film to which the light irradiation treatment has been implemented is heat-treated, from the viewpoint of promoting the reorientation of the molecular chain based on heating, the heating temperature is preferably set to more than 140°C, more preferably to 150°C to 250°C. The heating time is preferably 5 minutes to 200 minutes, more preferably 10 minutes to 60 minutes.
[0227] When manufacturing the liquid crystal alignment film, the following process may also be included: a process of contacting the coating film that has been subjected to light irradiation treatment with water, a water-soluble organic solvent, or a mixed solvent of water and a water-soluble organic solvent. Here, as a water-soluble organic solvent, for example, methanol, ethanol, 1-propanol, isopropyl alcohol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclopentanone can be mentioned. Among these, the solvent used in this process is preferably water, isopropyl alcohol, and a mixture thereof. As a contact method for the coating film and the solvent, for example, spraying, showering, immersion, and liquid coating can be mentioned, but are not limited to these. The contact time between the coating film and the solvent is not particularly limited, for example, 5 seconds to 15 minutes. The coating film can be heated after contact with the solvent.
[0228] (Step 3: Construction of Liquid Crystal Cell)
[0229] Two substrates with liquid crystal alignment films formed in the above manner are prepared, and liquid crystal is arranged between the two substrates arranged facing each other, thereby manufacturing a liquid crystal cell. When manufacturing a liquid crystal cell, for example, there are the following methods: (1) arranging the two substrates facing each other with a gap (spacer) between them so that the liquid crystal alignment films face each other, and bonding the peripheries of the two substrates together with a sealing material, injecting liquid crystal into the cell gap defined by the substrate surface and the sealing material, and then sealing the injection hole; (2) applying a sealing material to a predetermined portion of one substrate formed with a liquid crystal alignment film, then dripping liquid crystal at a predetermined number of locations on the liquid crystal alignment film surface, bonding the other substrate so that the liquid crystal alignment films face each other, and allowing the liquid crystal to spread over the entire surface of the substrates (one drop filling (ODF) method). Ideally, the manufactured liquid crystal cell is further heated to a temperature at which the liquid crystal used is isotropic and then slowly cooled to room temperature to remove the flow orientation during liquid crystal filling.
[0230] As sealing material, for example, epoxy resin containing alumina balls as spacers and hardeners can be used. As spacers, photoresist spacers (photospacer), bead spacers, etc. can be used. As liquid crystal, nematic liquid crystal (nematic liquid crystal) and disc-shaped liquid crystal (smectic liquid crystal) can be listed. Among these, nematic liquid crystal is preferably used, for example, it can be used: Schiff base (Schiff base) system liquid crystal, azoxy (azoxy) system liquid crystal, biphenyl system liquid crystal, phenylcyclohexane system liquid crystal, ester system liquid crystal, terphenyl (terphenyl) system liquid crystal, biphenylcyclohexane system liquid crystal, pyrimidine system liquid crystal, dioxane system liquid crystal, bicyclooctane system liquid crystal, cubic alkane (cubane) system liquid crystal, etc. In addition, cholesteric liquid crystal (cholesteric liquid crystal), chiral reagent, ferroelectric liquid crystal (ferroelectric liquid crystal) etc. can also be added to these liquid crystals for use.
[0231] When manufacturing a PSA-type liquid crystal element, first, a liquid crystal and a photopolymerizable compound are filled into the cell gap to construct a liquid crystal cell. After the liquid crystal cell is constructed, the following treatment is performed to impart a pretilt angle to the liquid crystal alignment film: while a voltage is applied between the conductive films on a pair of substrates, the liquid crystal cell is irradiated with light. Subsequently, to consume any photopolymerizable compound remaining in the liquid crystal, the liquid crystal cell is irradiated for a long period of time with light that is equal to or weaker than the light irradiation intended for imparting a pretilt angle, without applying a voltage. Specifically, the liquid crystal element is preferably manufactured using a method comprising the following steps.
[0232] [1] A step of forming a coating film using a liquid crystal alignment agent on each of the conductive films of a pair of substrates having conductive films (equivalent to the above-mentioned step 1)
[0233] [2] A step of constructing a liquid crystal cell by arranging a pair of substrates having coating films formed thereon with a liquid crystal layer containing a photopolymerizable compound interposed therebetween so that the coating films face each other (equivalent to the above-mentioned step 3)
[0234] [3] A step of irradiating the liquid crystal cell with light while a voltage is applied between the conductive films (first irradiation step)
[0235] [4] After the first irradiation step, a step of irradiating the liquid crystal cell with light having an intensity equal to or weaker than that of the light in the first irradiation step for a longer time than the first irradiation step and without applying a voltage across the conductive film (a second irradiation step)
[0236] As the photopolymerizable compound, a polyfunctional compound having a functional group capable of free radical polymerization, such as acryloyl, (meth) acryloyl, vinyl, etc., can be preferably used. From the viewpoint of reactivity, the photopolymerizable compound is preferably a polyfunctional (meth) acrylic compound having more than two (meth) acryloyl groups. In addition, from the viewpoint of stably maintaining the orientation of the liquid crystal molecules, as the photopolymerizable compound, a compound having a total of two or more cyclohexane rings and at least one of the benzene rings as the liquid crystal skeleton can be preferably used. In addition, as such a photopolymerizable compound, a previously existing compound can be used. When manufacturing a PSA type liquid crystal element, the proportion of the photopolymerizable compound used is, for example, 0.01 to 3 parts by mass, preferably 0.05 to 1 part by mass, relative to a total of 100 parts by mass of liquid crystal.
[0237] The voltage applied to the liquid crystal unit in the first irradiation step can be set to, for example, a direct current or alternating current of 5V to 50V. As the irradiated light, for example, ultraviolet rays and visible rays containing light with a wavelength of 150nm to 800nm can be used, preferably ultraviolet rays containing light with a wavelength of 300nm to 400nm. As the light source of the irradiated light, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. As the irradiation amount of light, 1,000J / m 2 Above and 200,000 J / m 2 Less than 1,000 J / m 2 ~100,000J / m 2 The intensity of the light irradiated to the liquid crystal cell in the first irradiation step is preferably 0.1 mW / cm 2 ~400mW / cm 2 The light irradiation time in the first irradiation step (also referred to as "UV1 time") is preferably 10 seconds to 200 seconds.
[0238] In the second irradiation step, the liquid crystal cell, which has been irradiated with light in the first irradiation step, is irradiated with light without applying a voltage. The light irradiated to the liquid crystal cell in the second irradiation step and the light source of the irradiating light are the same as those described for the first irradiation step. The intensity of the light irradiated to the liquid crystal cell in the second irradiation step is preferably 0.1 mW / cm 2 ~200mW / cm 2 , more preferably 0.1 mW / cm 2 ~100mW / cm 2 , and more preferably 0.1 mW / cm 2 ~30mW / cm 2 , and more preferably 0.1 mW / cm 2 ~5.0mW / cm2 The light irradiation time in the second irradiation step (also referred to as "UV2 time") is longer than the UV1 time, preferably 45 minutes to 200 minutes. 2 ), which may be equal to, more than, or less than the light irradiation in the first irradiation step. Furthermore, for example, if the light irradiation conditions in the first irradiation step and the second irradiation step are partially or entirely the same, the first irradiation step and the second irradiation step may be performed continuously.
[0239] In particular, when using the liquid crystal aligning agent disclosed herein to manufacture a PSA-type liquid crystal cell, the UV2 time can be shortened, thereby minimizing damage to the liquid crystal cell caused by light irradiation and shortening the manufacturing time.
[0240] Next, a polarizing plate is attached to the outer surface of the liquid crystal cell, if necessary. Examples of polarizing plates include a polarizing film called an "H film," which is formed by stretching and aligning polyvinyl alcohol while allowing it to absorb iodine, and sandwiched between a cellulose acetate protective film, or a polarizing plate consisting solely of the H film. This produces a liquid crystal cell.
[0241] The liquid crystal element disclosed herein can be effectively used in a variety of applications. Specifically, it can be used as various display devices such as clocks, portable game consoles, word processors, notebook personal computers, car navigation systems, camcorders, personal digital assistants (PDAs), digital cameras, mobile phones, smartphones, various monitors, liquid crystal televisions, and information displays, as well as in dimming devices and retardation films.
[0242] The present disclosure can provide the following means.
[0243] [Means 1] A liquid crystal alignment agent comprising: a first polymer comprising a polymer derived from 1 -W 1 " represented by the group (wherein, X 1 is a divalent linking group; W 1 is a monovalent group having a benzophenone structure; "*" represents a bonding bond) and has "*-X 1 -W 1" represented by the group; and the second polymer is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane and addition polymer and does not substantially contain a structural unit having a benzophenone structure, and at least one selected from the group consisting of the first polymer and the second polymer contains a group having a secondary amino group, a tertiary amino group, * 1 -NR 1 -* 2 and at least one nitrogen-containing structure in the group consisting of nitrogen-containing heterocyclic structures (wherein R 1 Is a monovalent detached group; "* 1 "and"* 2 " represents a structural unit of a diamine (bonded to a carbon atom excluding the carbon in the (thio)carbonyl group).
[0244] [Meanwhile,] the liquid crystal alignment agent according to [Meanwhile,] wherein the first polymer is at least one selected from the group consisting of polyamic acid and polyimide.
[0245] [Means 3] The liquid crystal alignment agent according to [Means 1] or [Means 2], wherein at least one selected from the group consisting of the first polymer and the second polymer contains a structural unit derived from a diamine having the nitrogen-containing heterocyclic structure.
[0246] [Means 4] The liquid crystal alignment agent according to any one of [Means 1] to [Means 3], wherein the first polymer is a polyamic acid.
[0247] [Means 5] A liquid crystal alignment agent according to any one of [Means 1] to [Means 4], wherein the second polymer is at least one selected from the group consisting of polyamic acid and polyimide, and contains structural units derived from tetracarboxylic anhydride, and among the structural units derived from the tetracarboxylic anhydride, the proportion of structural units derived from aromatic tetracarboxylic dianhydride is 50 mol% or less.
[0248] [Means 6] The liquid crystal alignment agent according to any one of [Means 1] to [Means 5], wherein at least one selected from the group consisting of the first polymer and the second polymer contains a structural unit having a vertical alignment group.
[0249] [Means 7] The liquid crystal alignment agent according to any one of [Means 1] to [Means 6], wherein at least one selected from the group consisting of the first polymer and the second polymer comprises a polymer having a *-NR bonded to an aromatic ring. 2 -CO- or *-CO-NR 2 -partial structure (wherein, R 2is a hydrogen atom or a monovalent organic group; "*" represents a bond to an aromatic ring).
[0250] [Meaning 8] The liquid crystal aligning agent according to any one of [Meaning 1] to [Meaning 7], further comprising a cross-linking agent.
[0251] [Means 9] The liquid crystal aligning agent according to any one of [Means 1] to [Means 8], wherein the liquid crystal aligning agent has "*-X 1 -W 1 The diamine of the group represented by " is represented by the above formula (CA-1).
[0252] [Means 10] A liquid crystal alignment agent comprising: a polymer comprising a polymer having "*-X 1 -W 1 " represented by the group (wherein, X 1 is a divalent linking group; W 1 is a monovalent group having a benzophenone structure; "*" represents a bonding bond) and has "*-X 1 -W 1 " represented by; and a cross-linking agent.
[0253] [Means 11] A liquid crystal alignment film formed using the liquid crystal alignment agent according to any one of [Means 1] to [Means 10].
[0254] [Means 12] A liquid crystal element comprising the liquid crystal alignment film described in [Means 11].
[0255] [Means 13] A compound represented by the above formula (CA-1-1).
[0256] [Example]
[0257] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the following Examples.
[0258] In the following examples, the imidization ratio of the polyimide and the molecular weight (Mw, Mn) of the polymer were measured by the following methods.
[0259] <Imidization ratio of polyimide>
[0260] The polyimide solution was added to pure water, the obtained precipitate was fully dried under reduced pressure at room temperature, and then dissolved in deuterated dimethyl sulfoxide. The H NMR spectra were performed at room temperature using tetramethylsilane as a reference substance. 1 H-Nuclear Magnetic Resonance, 1 H-NMR) determination. 1The imidization rate [%] was determined by analyzing the H-NMR spectrum and using the following formula (1).
[0261] Imidization rate [%] = (1-(β 1 / (β 2 ×α)))×100…(1)
[0262] (In formula (1), β 1 is the peak area of the proton origin of the NH group appearing near the chemical shift of 10 ppm, β 2 is the peak area of other proton sources, and α is the ratio of the number of other protons to one proton of the NH group in the polymer precursor (polyamic acid)
[0263] <Polymer molecular weight (Mw, Mn)>
[0264] The weight average molecular weight (Mw) and the number average molecular weight (Mn) were measured by gel permeation chromatography (GPC) under the following conditions.
[0265] Device: Showa Denko's "GPC-101"
[0266] GPC columns: Combination of "GPC-KF-801", "GPC-KF-802", "GPC-KF-803" and "GPC-KF-804" manufactured by Shimadzu GLC Co., Ltd.
[0267] Mobile phase: tetrahydrofuran (THF)
[0268] Column temperature: 40°C
[0269] Flow rate: 1.0 mL / min
[0270] Sample concentration: 1.0 mass%
[0271] Sample injection volume: 100 μL
[0272] Detector: Differential refractometer
[0273] Standard material: monodisperse polystyrene
[0274] The abbreviations of the compounds used in the following examples are shown below. In addition, for convenience, the "compound represented by formula (X)" may be simply referred to as "compound (X)".
[0275] (Tetracarboxylic dianhydride) TA-1 to TA-8
[0276] [Chemistry 16]
[0277]
[0278] (Diamine)DA-1~DA-10, daa-1~daa-3
[0279] [Chemistry 17]
[0280]
[0281] [Chemistry 18]
[0282]
[0283] (Diamine) DB-1~DB-12
[0284] [Chemistry 19]
[0285]
[0286] (Diamine) DC-1~DC-17
[0287] [Chemistry 20]
[0288]
[0289] (Other monomers, carboxylic acids) M-1 to M-9, S-1, C-1
[0290] [Chemistry 21]
[0291]
[0292] (Additives) AD-1~AD-10
[0293] [Chemistry 22]
[0294]
[0295] <Synthesis of Monomer>
[0296] [Synthesis Example 1A]
[0297] Compound (DA-3) was synthesized according to the following scheme.
[0298] [Chemistry 23]
[0299]
[0300] 3.85 mmol of 4-hydroxybenzophenone, 4.62 mmol of 3,5-dinitrobenzyl chloride, 4.62 mmol of potassium carbonate, and 8 mL of N,N-dimethylformamide (DMF) were added to a 50 mL eggplant flask. The reaction temperature was raised from room temperature to 80°C and stirred for 1 hour. After confirming the completion of the reaction by liquid chromatography-mass spectrometry (LC-MS), the mixture was cooled to room temperature. Thereafter, ethyl acetate and water were added for liquid separation and purification, and the organic layer was concentrated. The obtained purple solid was dried to obtain 1.45 g of compound (DA-3-1) (yield 99%).
[0301] Then, 3.83 mmol of compound (DA-3-1), 76.7 mmol of zinc powder, 38.3 mmol of ammonium chloride, 8.7 mL of tetrahydrofuran (THF) and 1.5 mL of ethanol (EtOH) were added to a 50 mL eggplant-shaped flask and cooled to 0°C in an ice bath. The reaction solution was stirred and 109 mmol of distilled water was added dropwise thereto. After stirring at 0°C for 10 minutes, the reaction temperature was raised to room temperature and stirred for 4 hours. After confirming that the reaction was complete by LC-MS analysis, zinc was removed by diatomaceous earth filtration. Ethyl acetate and water were added to the filtrate for liquid separation and purification, and the organic layer was concentrated. By drying the obtained solid, 1.16 g of the target diamine (DA-3) (yield 95%, loess-colored solid) was obtained. By 1 The structure of diamine (DA-3) was confirmed by H-NMR spectroscopy. 1 The H-NMR spectrum is shown in Figure 1 middle.
[0302] <Polymer Synthesis>
[0303] 1. Synthesis of polyamic acid
[0304] [Synthesis example 1]
[0305] 15 parts by mole of the tetracarboxylic dianhydride compound (TA-1) and 85 parts by mole of the compound (TA-3), and 30 parts by mole of the diamine compound (daa-1), 30 parts by mole of the compound (DB-12), 30 parts by mole of the compound (DC-14), and 10 parts by mole of the compound (DC-2) were dissolved in N-methyl-2-pyrrolidone (NMP), and the mixture was reacted at 60°C for 6 hours to obtain a solution containing 20% by mass of a polyamic acid (referred to as polymer (PAA-1)).
[0306] [Synthesis Example 2 to Synthesis Example 20]
[0307] Polyamic acids (polymers (PAA-2) to (PAA-20)) were obtained by the same procedures as in Synthesis Example 1, except that the types and amounts of the tetracarboxylic dianhydride and diamine compound used were changed as described in Table 1. In Table 1, the numerical values for the tetracarboxylic dianhydride (Dianhydride 1 to Dianhydride 3) represent the ratio (molar ratio) of each compound relative to 100 parts by mole of the total amount of tetracarboxylic dianhydride used in the synthesis of the polymer. The numerical values for the diamine compounds (Diamine 1 to Diamine 5) represent the ratio (molar ratio) of each compound relative to 100 parts by mole of the total amount of the diamine compounds used in the synthesis of the polymer.
[0308] 2. Synthesis of polyimide
[0309] [Synthesis Example 21]
[0310] 90 parts by mole of compound (TA-1) and 10 parts by mole of compound (TA-6) as tetracarboxylic dianhydride, and 10 parts by mole of compound (DA-6), 20 parts by mole of compound (DB-8), 20 parts by mole of compound (DC-14), 30 parts by mole of compound (DC-5), and 20 parts by mole of compound (DC-13) as diamine compounds were dissolved in NMP and reacted at 60°C for 6 hours to obtain a solution containing 20% by mass of polyamic acid. Subsequently, NMP was added to the obtained polyamic acid solution to prepare a solution having a polyamic acid concentration of 10% by mass, pyridine and acetic anhydride were added, and a dehydration ring-closure reaction was carried out at 80°C for 4 hours. After the dehydration ring-closure reaction, the solvent in the system was replaced with fresh NMP to obtain a solution containing 15% by mass of a polyimide (referred to as polymer (PI-1)) with an imidization rate of approximately 70%.
[0311] [Synthesis Example 22]
[0312] Except having changed the kind and amount of the tetracarboxylic dianhydride and the diamine compound used as described in Table 1, the same operation as in Synthesis Example 21 was carried out to obtain a polyimide (polymer (PI-2)).
[0313] [Table 1]
[0314]
[0315] 3. Synthesis of Styrene-Maleimide Copolymers
[0316] [Synthesis Example 23]
[0317] Under nitrogen, a 100 mL two-necked flask was charged with 40 mol parts of compound (M-2), 40 mol parts of compound (M-3), and 20 mol parts of compound (M-8) relative to a total of 100 mol parts of the polymerizable monomers; 0.3922 g of 2,2'-azobis(2,4-dimethylvaleronitrile) as a radical polymerization initiator (10 parts by mass relative to a total of 100 parts by mass of the polymerizable monomers); and 15.68 g of N-methyl-2-pyrrolidone (NMP) as a solvent (400 parts by mass relative to a total of 100 parts by mass of the polymerizable monomers). Polymerization was then carried out at 70°C for 6 hours. After reprecipitation in methanol, the precipitate was filtered and vacuum-dried at room temperature for 8 hours to obtain the target addition polymer (referred to as polymer (PM-1)).
[0318] [Synthesis example 24]
[0319] Except for changing the type and amount of the polymerizable monomers used as described in Table 2, the same operation as in Synthesis Example 23 was carried out to obtain an addition polymer (referred to as polymer (PM-2)).
[0320] [Table 2]
[0321]
[0322] 4. Synthesis of polyorganosiloxane
[0323] [Synthesis Example 25]
[0324] In a 1000mL three-necked flask, 100.0g of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (compound (S-1)), 500g of methyl isobutyl ketone and 10.0g of triethylamine were placed and mixed at room temperature. Subsequently, 100g of deionized water was added dropwise from a dropping funnel over a period of 30 minutes, mixed under reflux and reacted at 80°C for 6 hours. After the reaction was completed, the organic layer was taken out and washed with a 0.2% by mass aqueous solution of ammonium nitrate until the washed water became neutral, and then the solvent and water were distilled off under reduced pressure. An appropriate amount of methyl isobutyl ketone was added to obtain a 50% by mass solution of a polyorganosiloxane having an epoxy group (set to "polymer (PS-1)").
[0325] [Synthesis Example 26]
[0326] Polymer (PS-1) was obtained in the same manner as in Synthesis Example 25. A 500 mL three-necked flask was charged with 20 mol% of compound (C-1) relative to the amount of epoxy groups in polymer (PS-1), 1.00 g of tetrabutylammonium bromide, 20.0 g of a solution containing polymer (PS-1), and 290.0 g of methyl isobutyl ketone, and the mixture was stirred at 90° C. for 18 hours. After cooling to room temperature, the liquid separation and washing operation was repeated 10 times with distilled water. Thereafter, the organic layer was recovered, and concentration and dilution with NMP were repeated twice using a rotary evaporator. The solid content concentration was adjusted to 10% by mass using NMP to obtain an NMP solution of polyorganosiloxane (hereinafter referred to as polymer (PS-2)).
[0327] [Table 3]
[0328]
[0329] <Preparation and Evaluation of Liquid Crystal Alignment Agents>
[0330] [Example 1]
[0331] 1. Preparation of liquid crystal alignment agent
[0332] A solution containing 50 parts by mass of the polymer (PAA-11) obtained in Synthesis Example 11 was mixed with a solution containing 50 parts by mass of the polymer (PAA-6) obtained in Synthesis Example 6. The mixture was then diluted with N-methyl-2-pyrrolidone (NMP), γ-butyrolactone (GBL), butyl cellosolve (BC), diacetone alcohol (DAA), and diethylene glycol diethyl ether (DEDG) to prepare a solution having a solvent composition of NMP / GBL / BC / DAA / DEDG = 30 / 30 / 15 / 15 / 10 (mass ratio) and a solids concentration of 3.5% by mass. The solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal aligning agent (AL-1).
[0333] 2. Preparation of Liquid Crystal Composition
[0334] To 10 g of nematic liquid crystal (MLC-6608 manufactured by Merck), 5% by mass of a liquid crystal compound represented by the following formula (L1-1) and 0.3% by mass of a photopolymerizable compound represented by the following formula (L2-1) were added and mixed to obtain a liquid crystal composition LC1.
[0335] [Chemistry 24]
[0336]
[0337] 3. Preparation of Insulating Film-Forming Composition
[0338] A flask equipped with a cooling tube and a stirrer was charged with 7 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile), 200 parts by mass of propylene glycol monomethyl ether acetate, 15 parts by mass of methacrylic acid, 30 parts by mass of glycidyl methacrylate, 20 parts by mass of styrene, 5 parts by mass of 2-hydroxyethyl acrylate, and 30 parts by mass of isobornyl acrylate. After nitrogen substitution, stirring was slowly initiated. The reaction solution was raised to 62°C and maintained at this temperature for 5 hours to obtain a polymer solution containing the acrylic copolymer (R-1). The obtained polymer solution was added dropwise to 900 parts by mass of hexane to precipitate the acrylic copolymer (R-1). The precipitated acrylic copolymer (R-1) was separated, and 150 parts by mass of propylene glycol monomethyl ether acetate was added. The mixture was heated to 40°C and subjected to reduced pressure distillation to obtain a polymer solution containing the acrylic copolymer (R-1). The obtained polymer solution containing the acrylic copolymer (R-1) had a solid content concentration of 30% by mass, and the area of unreacted monomers and polymerization initiators was 2.3% as determined by GPC analysis. The weight average molecular weight (Mw) was 12,800.
[0339] With respect to 100 parts by mass (solid content) of the acrylic copolymer (R-1), 25 parts by mass of a condensate of 4,4'-[1-[4-[1-[4-hydroxyphenyl]-1-methylethyl]phenyl]ethylene]bisphenol (1.0 mol) and 1,2-naphthoquinonediazide-5-sulfonyl chloride (2.0 mol) as a photosensitizer, 5 parts by mass of a mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate ("KAYARAD DPHA" manufactured by Nippon Kayaku Co., Ltd.) as a polymerizable compound, and 10 parts by mass of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (Kyowa Hakko Co., Ltd.) as a film-forming aid were added. Kirin) and SH28PA (Dow Corning Toray Co., Ltd.) as a leveling agent were mixed, dissolved in a mixture of diethylene glycol ethyl methyl ether so that the solid content concentration became 18% by mass, and then filtered using a membrane filter with a pore size of 0.2 μm to prepare a composition for forming an insulating film (RD-1).
[0340] 4. Preparation of PSA-Type Liquid Crystal Cell for Evaluation
[0341] The liquid crystal alignment agent (AL-1) prepared in the above-mentioned process is applied to the transparent electrode surface of a glass substrate having a transparent electrode including an ITO film using a spinner, and pre-baked on a hot plate at 80°C for 1 minute. The solvent is then removed by heating at 200°C for 1 hour in an oven replaced with nitrogen, thereby forming a coating film (liquid crystal alignment film) with a thickness of 0.08 μm, thereby obtaining a pair (two) of substrates having liquid crystal alignment films.
[0342] An epoxy resin adhesive containing 3.5μm-diameter alumina spheres was screen-printed around the periphery of the surface of one of the substrates having the liquid crystal alignment film. The liquid crystal alignment film surfaces of the two substrates were then placed facing each other, overlapped, and pressure-bonded. The adhesive was then heated at 150°C for one hour to thermally cure. Subsequently, the gap between the substrates was filled with liquid crystal composition LC1 through the liquid crystal injection port. The liquid crystal injection port was then sealed with an epoxy adhesive. Furthermore, to remove flow alignment during liquid crystal injection, the system was heated at 150°C for 10 minutes and then slowly cooled to room temperature.
[0343] Next, the obtained liquid crystal cell was subjected to an ultraviolet irradiation device using a metal halide lamp as a light source at a rate of 50,000 J / m2 while applying 10 V AC at a frequency of 60 Hz between the electrodes to drive the liquid crystal. 2 The liquid crystal cell after the first irradiation was irradiated with ultraviolet light at an intensity of 3.22 mW / cm2 (first irradiation). The irradiation amount was measured using a light meter with a wavelength of 365 nm as the reference. Subsequently, the liquid crystal cell after the first irradiation was irradiated with the same ultraviolet irradiation device as the first irradiation at an intensity of 3.22 mW / cm2 without applying a voltage between the electrodes. 2 Irradiate with ultraviolet light for 100 minutes (=UV2 time) (second irradiation). The first irradiation is for imparting a tilt angle to the liquid crystal near the organic film formed by the liquid crystal alignment agent, while the second irradiation is for consuming the photopolymerizable compound remaining in the liquid crystal. Thus, a PSA-type liquid crystal cell is manufactured.
[0344] 5. Evaluation of tilt-giving properties
[0345] Using the PSA liquid crystal unit for evaluation manufactured in 4., according to the method described in the non-patent literature "TJ Scheffer et al., Journal of Applied Physics, J.Appl.Phys., Vol. 48, p. 1783 (1977)" and "F. Nakano et al., Japanese Journal of Applied Physics, JPN.J.Appl.Phys., Vol. 19, p. 2013 (1980)", the value of the tilt angle of the liquid crystal molecules relative to the substrate surface is measured by the crystal rotation method using He-Ne laser light, and the value is set as the pretilt angle. The pretilt angle of the PSA-type liquid crystal cell used for evaluation was judged as "good (○)" if it was less than 88.5°, "acceptable (△)" if it was 88.5° or more and less than 89.0°, and "poor (×)" if it was 89.0° or more. The tilt-imparting properties of the above examples were judged as "good (○)".
[0346] 6. Evaluation of the light irradiation time (UV2 time) in the second irradiation
[0347] The evaluation PSA type liquid crystal unit was manufactured in the same manner as in 4. except that the ultraviolet irradiation time (UV2 time) in the second irradiation was changed from 100 minutes to 50 minutes. For the evaluation PSA type liquid crystal unit, the value of the tilt angle of the liquid crystal molecules relative to the substrate surface was measured by the rotational crystallization method using He-Ne laser light in the same manner as in "5. Evaluation of the tilt imparting property", and the tilt angle was set as the pretilt angle. The measurement was performed on the pretilt angle before voltage was applied to the liquid crystal unit (set as the "initial pretilt angle θini") and the pretilt angle after driving for 48 hours at room temperature with an alternating current (AC) of 9V and a backlight (set as the "pretilt angle after driving θac"). In addition, the measured initial pretilt angle θini and the pretilt angle after driving θac were used to calculate the pretilt angle change rate β[%] by the following formula (y).
[0348] β[%]=[(θac-θini / θini)]×100…(y)
[0349] The UV2 time is the light irradiation time required to consume the photopolymerizable compound in the liquid crystal layer. If the desired pretilt angle can be achieved while shortening this time, the liquid crystal cell can be considered good if the UV2 time can be shortened. A pretilt angle change rate β of less than 3% is evaluated as "good (○)", a pretilt angle change rate of 3% or more but less than 5% is evaluated as "acceptable (△)", and a pretilt angle change rate of 5% or more is evaluated as "poor (×)". The UV2 time of the example described above was rated "good (○)".
[0350] 7. Evaluation of sealing material adhesion
[0351] The liquid crystal alignment agent (AL-1) was applied to a glass substrate using a spinner, and pre-baked for 2 minutes using a hot plate at 80°C, and then heated (post-baked) for 30 minutes in a 230°C oven with nitrogen substituted in the box to form a coating film (liquid crystal alignment film) with an average film thickness of 0.10 μm. Two glass substrates with a coating film were prepared by repeating the same operation as described above. An ODF sealing material (manufactured by Sekisui Chemical Co., Ltd., S-WB42) was applied to the coating film of one glass substrate with a coating film in a manner that the width became 0.5 mm, and the coating film of another glass substrate was bonded in such a manner that it was in contact with the ODF sealing material. Thereafter, a metal halide lamp was used to irradiate 30,000 J / m 2 After irradiation with light (365 nm equivalent), the sealant was heated in an oven at 120° C. for 1 hour. The sealant was then evaluated for adhesion by measuring adhesion strength using a tensile compression tester (model: SDWS-0201-100SL) manufactured by Imada Manufacturing Co., Ltd.
[0352] Regarding the evaluation, the adhesion force is 180N / cm 2 The above cases were rated as "good (○)", and 150 N / cm 2 More than but less than 180N / cm 2 If the load is less than 150 N / cm, set it as "OK (△)". 2 As a result, the sealant adhesiveness of the above-mentioned Example was evaluated as "good (○)".
[0353] 8. Production of Liquid Crystal Cell for Impurity Resistance Evaluation
[0354] A glass substrate with a comb-shaped ITO electrode patterned thereon and a glass substrate without an electrode were prepared. The insulating film-forming composition (RD-1) was applied to the glass substrate without an electrode using a spin coater and pre-baked on a hot plate at 90°C for 2 minutes. The entire surface of the substrate was then irradiated with 300 mJ / cm using a proximity exposure machine (Canon's "MA-1200" (GHI-ray hybrid)). 2After being exposed to light of 100 μm, the film was cured by heating (post-baking) at 230° C. in an oven for 30 minutes to form an insulating film with a thickness of 3 μm on the glass substrate.
[0355] A liquid crystal alignment agent (AL-1) was applied using a spinner to the electrode-forming surface of a substrate provided with an ITO electrode patterned into a comb-teeth shape and the insulating film-forming surface of a substrate including an insulating film, respectively. The mixture was pre-baked on an 80°C hotplate for 1 minute. Subsequently, the mixture was heated at 230°C for 1 hour in an oven purged with nitrogen, thereby producing a pair (two substrates) having a liquid crystal alignment film with a thickness of 0.1 μm.
[0356] After applying an epoxy resin adhesive to which aluminum oxide balls with a diameter of 3.5 μm are added to the periphery of the surface of the substrate having the liquid crystal alignment film of the substrate including the insulating film by screen printing, the liquid crystal alignment film surfaces of a pair of substrates are faced to each other and pressed together, and the adhesive is thermally cured at 150°C for 1 hour. Subsequently, the liquid crystal composition LC1 is filled into the gap between the substrates from the liquid crystal injection port, and then the liquid crystal injection port is sealed with an epoxy adhesive. Furthermore, in order to remove the flow orientation during liquid crystal injection, it is heated at 130°C and then slowly cooled to room temperature to manufacture a liquid crystal cell for evaluating impurity resistance. In addition, since the substrate is easy to prepare, the liquid crystal cell for evaluating impurity resistance is prepared using an electrode substrate for an IPS type liquid crystal cell.
[0357] 9. Evaluation of impurity resistance based on voltage holding ratio (VHR)
[0358] The liquid crystal cell for evaluating impurity resistance produced in 8. was allowed to stand in an oven at 60°C. The voltage holding ratio (VHR) was then measured using a VHR measuring device "VHR-1" manufactured by Toyo Technica under the conditions of 1 V and 1670 milliseconds. A VHR exceeding 60% was rated "good (○)", a VHR between 60% and 45% was rated "acceptable (△)", and a VHR below 45% was rated "poor (×)". The results showed that the impurity resistance of the above example was rated "good (○)" based on VHR.
[0359] 10. Evaluation of impurity resistance based on residual DC
[0360] For the liquid crystal unit for evaluating the resistance to impurities manufactured in 8., after driving with AC 2.5V and setting the brightness difference between any two pixels to 0, it is driven with AC 2.5V and DC 1V is applied to only one of the pixels for 20 minutes to accumulate charge. When the application of DC 1V is terminated and the drive is returned to AC 2.5V only, a brightness difference is generated between the two pixels by the accumulated charge. The relaxation time of the residual DC value attenuation process is calculated by observing the change of the brightness difference over time. The case where the relaxation time is less than 10 seconds is judged as "good (○)", the case where the relaxation time is more than 10 seconds and less than 30 seconds is judged as "acceptable (△)", and the case where the relaxation time is more than 30 seconds is judged as "poor (×)". As a result, the impurity resistance based on residual DC of the embodiment is evaluated as "good (○)".
[0361] [Example 2 to Example 14 and Comparative Examples 1 to Comparative Examples 7]
[0362] The liquid crystal alignment agent was prepared in the same manner as in Example 1 except that the types and amounts of polymers and additives used in the preparation of the liquid crystal alignment agent were changed as shown in Table 4. Furthermore, using the obtained liquid crystal alignment agent, a liquid crystal cell for evaluation was manufactured in the same manner as in Example 1, and various evaluations were performed. The evaluation results are shown in Table 4. In Table 4, the values in the polymer column and the additive column represent the blending ratio (parts by mass) of each compound in terms of solid content relative to 100 parts by mass of the total amount of the polymer component used in the preparation of the liquid crystal alignment agent.
[0363] [Table 4]
[0364]
[0365] As shown in Table 4, the tilt imparting property, UV2 time, sealing material adhesion and impurity resistance of the liquid crystal aligning agents of Examples 1 to 14 are all evaluated as good (○) or acceptable (△), and various characteristics are balanced. In contrast, in Comparative Examples 1 to 4, which do not contain a polymer containing a structural unit derived from a specific diamine (first diamine) having a benzophenone structure, the tilt imparting property, UV2 time, sealing material adhesion and impurity resistance are evaluated as poor (×), which is worse than Examples 1 to 14. In addition, in Comparative Example 5, which only uses a polymer that does not contain a structural unit having a specific nitrogen-containing structure, the impurity resistance is evaluated as poor. Furthermore, when Comparative Example 6 and Comparative Example 7, which contain only one polymer, are compared with Examples 1 to 14, in Comparative Example 6, the impurity resistance using VHR as an indicator is poor, and in Comparative Example 7, the sealing material adhesion is evaluated as poor.
[0366] From the above results, it is clear that the liquid crystal aligning agent of the present disclosure can obtain a liquid crystal aligning film having excellent foreign matter resistance, tilt imparting properties, and sealant adhesion, and can shorten the light irradiation time for consuming the photopolymerizable compound when producing a PSA type liquid crystal element.
Claims
1. A liquid crystal alignment agent, comprising: The first polymer comprises a polymer derived from 1 -W 1 " represents a diamine structural unit, and has "*-X 1 -W 1 " represents a base, wherein X 1 is a divalent linking group; W 1 is a monovalent group having a benzophenone structure; "*" represents a bonding bond; and The second polymer is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane and addition polymer and substantially does not contain a structural unit having a benzophenone structure. At least one of the first polymer and the second polymer comprises a 1 -NR 1 -* 2 and a structural unit of at least one nitrogen-containing diamine in the group consisting of a nitrogen-containing heterocyclic structure, wherein R 1 It is a monovalent dissociative group; "* 1 "and"* 2 " represents a bond to a carbon atom excluding the carbon in the (thio)carbonyl group.
2. The liquid crystal alignment agent according to claim 1, wherein The first polymer is at least one selected from the group consisting of polyamic acid and polyimide.
3. The liquid crystal alignment agent according to claim 1, wherein At least one selected from the group consisting of the first polymer and the second polymer includes a structural unit derived from a diamine having the nitrogen-containing heterocyclic structure.
4. The liquid crystal alignment agent according to claim 1, wherein The first polymer is polyamic acid.
5. The liquid crystal alignment agent according to claim 1, wherein The second polymer is at least one selected from the group consisting of polyamic acid and polyimide, and includes a structural unit derived from tetracarboxylic anhydride. Among the structural units derived from the tetracarboxylic anhydride, the ratio of the structural units derived from aromatic tetracarboxylic dianhydride is 50 mol% or less.
6. The liquid crystal alignment agent according to claim 1, wherein At least one selected from the group consisting of the first polymer and the second polymer includes a structural unit having a vertical alignment group.
7. The liquid crystal alignment agent according to claim 1, wherein: At least one selected from the group consisting of the first polymer and the second polymer comprises a polymer having a *-NR bonded to an aromatic ring. 2 -CO- or *-CO-NR 2 - a structural unit of a diamine of a partial structure, wherein R 2 It is a hydrogen atom or a monovalent organic group; "*" indicates a bond to the aromatic ring. The liquid crystal aligning agent according to claim 1 , further comprising a cross-linking agent.
9. The liquid crystal alignment agent according to claim 1, wherein: With "*-X 1 -W 1 The diamine of the group represented by " is represented by the following formula (CA-1); In the formula (CA-1), X 1 is a divalent linking group; X 2 Is a single key or has "*-X 1 -W 1 " represents a divalent radical of a partial structure; R 5 and R 6 are independently monovalent substituents; r1 is an integer of 0-4; and r2 is an integer of 0-5.
10. A liquid crystal alignment agent comprising: Polymers, including those derived from 1 -W 1 " represents a diamine structural unit, and has "*-X 1 -W 1 " represents a base, wherein X 1 is a divalent linking group; W 1 is a monovalent group having a benzophenone structure; "*" represents a bonding bond; and Cross-linking agent. 11 . A liquid crystal alignment film, formed using the liquid crystal alignment agent according to claim 1 . 12 . A liquid crystal element comprising the liquid crystal alignment film according to claim 11 .
13. A compound represented by the following formula (CA-1-1); In the formula (CA-1-1), R 8 is an alkanediyl group having 1 to 10 carbon atoms; Z 1 is an oxygen atom or -NR 9 -; R 9 is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group; R 5 and R 6 are independently monovalent substituents; r1 is an integer of 0-4; and r2 is an integer of 0-5.
Citation Information
Patent Citations
Liquid crystal aligning agent and liquid crystal display element
JP2010097188A
Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element
WO2015033921A1
